Complexation with β-cyclodextrin derivatives enhanced the bioavailability of quercetin through improving solubility and inhibiting recrystallization - Qiao Chen; Hai-Xia Xu; Ji-Guang Chen; Lin Dai; Bao-Geng Fu; Qing-Feng Zhang (Journal of Food Engineering, 2027)

Storage characteristics evaluation of late-maturing Actinidia arguta resources pollinated by different male pollens - Qinjia Zhao; Lin Hui; Huanyu Wang; Miao Yan; Guanlin Qian; Heran Xu; Naizhu Liu; Guang Xin; Song Pan (Postharvest Biology and Technology, 2027)

A teleost hepcidin derived peptide mSshep 2: Protection against Edwardsiella piscicida infection via preservation of intestinal integrity, modulation of immune responses, and regulation of gut microbiota - Hao Jing; Guang-hua Wang; Zhi-shu Zhu; Nuo Sun; Kai Yang; Zi-yue Chen; Yi-lin Du; Zi-qi Wang; Min Zhang (Aquaculture, 2027)

Cyclic regeneration and up-concentration for nitrate recovery from wastewater via in situ NaNO3 generation under saline, fully autotrophic nitrification conditions - Molin Lian; Zihang Ma; Guang Chen; Siqi Yu; Qing Xia; Bingjie Lin; Xiangdong Xu; Rui Tang; Zhen Zhou (Bioresource Technology, 2026)

Enhancing herbaceous biomass combustion in an industrial-scale CFB boiler using iron-based oxygen carriers as bed material - Guang Sun; Lin Li; Chong Liu; Tianxin Li; Heng Liu; Lunbo Duan (Fuel, 2026)

A TFPI-1 homolog from Sebastes schlegelii: Characterization of C-terminal endogenous cleavage and antimicrobial role of derived peptide - Zhi-Shu Zhu; Zi-Yue Chen; Guang-Hua Wang; Hao Jing; Kai Yang; Nuo Sun; Yi-Lin Du; Zi-Qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Precursor rigidity engineering enables synergistic regulation of closed pores and graphitic domains for balancing energy and power densities in hard carbon anodes - Qiaofeng Huang; Yiwen Sun; Haoliang Lin; Yuhai Wang; Yifan Sha; Weizhen Fan; Litao Shi; Yu Ying; Xianjian Duan; Chunlei Wu; Guang Shi (Chemical Engineering Journal, 2026)

Biological fire prevention through fungal degradation: Armillaria mellea alters combustibility of surface fuels in typical China Three-North forests - Furui Jian; Lixuan Wang; Dongming Ye; Guang Yang; Fengjun Zhao; Lin Zhang (Biomass and Bioenergy, 2026)

Nitrogen and straw optimization boosts rice growth via arbuscular mycorrhizal fungal communities and soil ecological functions - Rui Chen; Ning Wang; Pei Chen; Yu Cheng; Jian-Guang Yu; Li-Hong Xue; Lin-Zhang Yang (Applied Soil Ecology, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Role of pectin degree of esterification in the structural assembly and oxidative stability of WPI–citrus Pectin–EGCG conjugates stabilized emulsion - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Food Hydrocolloids, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Antagonistic effects of PM2.5 and ozone on respiratory morbidity: A multi-pollutant interaction analysis using outpatient data from China's Pearl River Delta - Shui-Yue Lu; Xue-Dan Xu; Dao-Qin Wang; Muhammad Amjad; Guang-Hui Dong; Li-Zi Lin; Hong-Wei Tu (Atmospheric Environment, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

An immersed boundary-recursive regularized lattice Boltzmann method for flow-induced noise prediction with moving bodies - Lei Jin; Guang-yu Shi; Chun-yu Guo; Lin Cai; Lu-cheng Sun; Yuan-jian Yao (Ocean Engineering, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Hepatic immunometabolic reprogramming of Sebastes schlegelii in response to Photobacterium damselae subsp. piscicida infection: biochemical, transcriptomic and metabolomic analyses - Hao Jing; Guang-hua Wang; Kai Yang; Zi-yue Chen; Zhi-shu Zhu; Nuo Sun; Yi-lin Du; Zi-qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

The oxidative potential of PM2.5 outperforms its mass concentration in association with childhood sleep disorders: Evidence from a large-scale study in China - Yun-Hui Shao; Dan Cai; Qian Yao; Xi-Hua Lin; Jin-Shan Ge; Lu-Yin Wu; Yun-Jiang Yu; Guang-Hui Dong; She-Xia Ma (Environmental Pollution, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Hydraulic conductivity and the associated xylem anatomy as reliable predictors of tree productivity for Populus species along the fast-slow spectrum - Attaullah Khan; Xue-Wei Gong; Jing-Jing Guo; Cheng-Lin Yuan; Shen-Hao Song; Zhong-Yi Pang; Yan-Hui Peng; Xue-Kai Sun; Guang-You Hao (Agricultural and Forest Meteorology, 2026)

Semi-permeable membrane coverage accelerates composting through modulated bacterial succession and organic matter transformation - Fu-Sheng Sun; Chao Wang; Nader Mohamed; Lin Shi; Bo-Hao Yin; Yue-Bing Sun; Guang-Hui Yu (Waste Management, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Co-activation and signal crosstalk between parthanatos and mitophagy in light-induced retinal injury - Yu-Lin Li; Si-Ming Zhang; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Strengthening impact of Indian Ocean Basin Mode on ENSO under greenhouse warming - Xia Zhao; Guang Yang; Dongliang Yuan; Lin Liu; Yazhou Zhang; Baochao Liu; Zhengyi Zhang (Global and Planetary Change, 2026)

Sedimentation rate changes revealing the evolution of circum–Arctic ice sheets since the Last Interglacial - Song Zhao; Dong Wu; Yu-Ying Zhang; Chao Cui; Sen Shan; Peng Ren; Lin-Sen Dong; Wei-Bin Zhang; Shu-Wei Sun; Yan-Guang Liu (Global and Planetary Change, 2026)

Thallium isotope constraints on transient oxygenation and prolonged anoxia during the Late Silurian Lau Event - Yuping Zhou; Jiří Frýda; Yi-Bo Lin; Lulu Wang; Mengchun Cao; Guang-Yi Wei; Fei Wu; Yi Wang; Shu-zhong Shen; Feifei Zhang (Geochimica et Cosmochimica Acta, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Seismic behavior of novel multi-celled composite shear walls with energy-dissipating corrugated steel plates - Dai-Jiang Zhou; Xian Li; Chen-Ze Li; Zi-Lin Zhang; Xi-Guang Liu; Ming Chen (Engineering Structures, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

The degradation of proanthocyanidins: dynamic mechanisms to digital solutions - Naizhu Liu; Li Li; Yafei Wang; Zhenshan Hou; Lin Hui; Yunting Li; Guanlin Qian; Rongrong Xia; Miao Yan; Heran Xu; Jinghong Shan; Huanyu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Estimating hydraulic conductivity based on a backbone curve model - Jia-Bin Li; Yun-Hua Li; Ming-Guang Li; Jin-Jian Chen; Yong-Mao Hou; Guan-Lin Ye (Transportation Geotechnics, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Mechanically robust and electrolyte-stable 2D MOF-based nanocomposite membrane with rich low-resistance highways for high-performance osmotic energy harvesting - Chia-An Lung; Guang Hui Teoh; Wen-Hung Lin; Kalon Gopinadhan; Soorathep Kheawhom; Li-Hsien Yeh (Chemical Engineering Journal, 2026)

Melatonin Modulates Antioxidant Properties, Carotenoid Accumulation, and Lignin Deposition to Enhance Adaptability to Salt Stress in Carrot - Guang-Long Wang; Yu-Jie Xu; Wang-Qi Jin; Lin-Yan Jia; Xu-Qin Ren; Ya-Nan Chen; Ai-Sheng Xiong (Journal of Plant Growth Regulation, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Innovative approaches to carbon capture using fluidized bed reactors: A brief review - Yuanqiang Duan; Lin Li; Dennis Lu; Shuo Zhang; Guang Sun; Zhengkun Sun; Lunbo Duan (Fuel, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

High entropy alloy-a promising candidate in sensor: Synthesis strategies, working mechanisms, recent progress, and promising perspectives - Yuanchao Lu; Guang Zheng; Chanjuan Dai; Ningxiang Yu; Xiaohua Nie; Lin Zhang; Xianghe Meng (Chemical Engineering Journal, 2026)

Reactive-oxygen-species-unlocking fusogenic liposome for spatially-selectively cytoplasmic antioxidant delivery and synergistic acute liver injury treatment - Yongkang Du; Huimin Kong; Huijuan Zheng; Xiaobing Lin; Tinghua Lu; Yingting Zhao; Ke Wang; Jiadong Zhou; Ruihua Huang; Shengchun Zhang; Guang Shi; Chunxiong Zheng; et al. (Chemical Engineering Journal, 2026)

A hollow mesoporous Prussian blue-cerium oxide-based oxygenating nanosystem for microenvironment remodeling in rheumatoid arthritis - Xiuke Lin; Yun Liu; Huiyi Wu; Wenyi Guang; Hua Song (Chemical Engineering Journal, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Ocean acidification reduces diatom and photosynthetic gene abundance on plastic in an coastal bay mesocosm experiment - Zheng Chen; Dorsaf Kerfahi; XueQian He; Xu Zhang; Ping Zhang; Guang Gao; Kunshan Gao; Jason M. Hall-Spencer; Jonathan M. Adams; Xin Lin (Marine Environmental Research, 2026)

Site cooperation of copper-silica interfacial Cu+/Cuσ+ species boosts low-temperature chemoselective hydrogenation of functionalized nitroarenes - Guang Xian Pei; Mengdi Guo; Lin Li; Hong Wen Guo; Haifeng Qi; Haisheng Wei; Xiao Yan Liu; Yousheng Yin (Chemical Engineering Journal, 2026)

The light side of the microbiome in trauma: Mechanism and applications - Han-Yue Luo; Lei-Ming Cao; Kan Zhou; Yi-Fu Yu; Yao Xiao; Guang-Rui Wang; Bing Liu; Qiu-Ji Wu; Xiao-Long Wang; Zhi-Yong Song; Lin-Lin Bu (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Correction to: Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Methyl jasmonate enhances carotenoid accumulation and lignin deposition in carrot taproot - Guang-Long Wang; Jia-Qi Wu; Yan-Xin Ge; Lin-Yan Jia; Cheng-Ling Zhou; Xu-Qin Ren; Ai-Sheng Xiong (Protoplasma, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Diagenetic effects on cerium isotope fractionation in marine carbonates: Toward calibrating carbonate Ce isotopes as a paleoredox proxy - Kai Sheng; Mengchun Cao; Yi-Bo Lin; Ryoichi Nakada; Guang-Yi Wei; Xiaobin Cao; Shu-zhong Shen; Feifei Zhang (Geochimica et Cosmochimica Acta, 2026)

Antimicrobial peptide mSshep 1 from Sebastes schlegelii combines broad-spectrum antibacterial activity, membrane-disruptive mechanism and in vivo protective efficacy - Hao Jing; Guang-hua Wang; Kai Yang; Zi-yue Chen; Zhi-shu Zhu; Nuo Sun; Yi-lin Du; Zi-qi Wang; Min Zhang (Fish & Shellfish Immunology, 2026)

Rab10 GTPase from the mud crab Scylla paramamosain is involved in the host immune response against V. parahaemolyticus infection - Chang-Hong Cheng; Hai-Peng Qin; Si-Gang Fan; Hong-Ling Ma; Guang-Xin Liu; Dong-Lin Yao; Wen-Fan Luo; Xian-Feng Yang; Zhi-Xun Guo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

Gene Regulatory Networks Controlling Fruit Anthocyanin Accumulation: A Review - Da Zhang; Bowei Zhu; Xin Liu; Han Wang; Guodong Zhao; Lin’guang Jia; Dongmei Chen; Tongsheng Zhao; Gang Niu; Chaohong Zhang; Xinsheng Zhang (Applied Fruit Science, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Integrated basin-scale assessment of legacy and emerging PFAS in the Xiangjiang River Basin, China: Occurrence, source apportionment, and risk prioritization - Da-Ying Lin; Li-Xin Hu; You-Sheng Liu; Jin-Na Zhang; Guang-Guo Ying (Water Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Solidago canadensis alters rhizosphere bacterial communities of Artemisia argyi under warming and nitrogen deposition—invaded rhizospheres become similar to the invader's - Yong-Feng Wang; Yun-Long Zhang; Ying Li; Guang-Qian Ren; Shan-Shan Qi; Bi-Ying Zhao; Zhi-Cong Dai; Dao-Lin Du (Plant and Soil, 2026)

On-exosome-membrane DNA polymerization-powered magneto-electrochemical aptasensing for osteosarcoma - Guang-Xian Zhong; Huang-Feng Lin; Fei-Huan Fu; Jing-Wei Zhou; Chong-Yu Chen; Chao-Yang Wu; Jian-Ping Lin; Xiong-Wei Xu; Jian-Hua Lin; Jin-Yuan Chen (Analytica Chimica Acta, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Bulk metagenomics and machine learning unravels nitrogen metabolism patterns in extreme-temperature marine environments - Zheng Guo; Yong-Guang Li; Xiao-Lin Liu; Zhao-Jie Teng; Qi-Long Qin; Qian-Qian Cha; Zhi-Bin Wang; Shou-Qing Ni (Bioresource Technology, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Henmt1 is indispensable for female fertility in Nile tilapia - Ma Zhuo; Chen Lin; Zhen Xu; Jie Yang; Guang Xu; Ying Chen; Deshou Wang; Wenjing Tao (Aquaculture, 2026)

Rational design of Whey protein–polysaccharide delivery systems: Synergistic mechanisms and advanced applications - Guang-Lin Luo; Ping-Ping Wang; Chun Chen; Xiong Fu (Trends in Food Science & Technology, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Corrigendum to “Hierarchical-structured bacterial cellulose/potato starch tubes as potential small-diameter vascular grafts” [Carbohydrate Polymers 281 (2022) 119034] - Li Liu; Xiongfa Ji; Lin Mao; Li Wang; Kun Chen; Zhijun Shi; Abeer Ahmed Qaed Ahmed; Sabu Thomas; Revin Victor Vasilievich; Lin Xiao; Xiaohong Li; Guang Yang (Carbohydrate Polymers, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Controls and contributions of methylotrophic methanogenesis to methane production in coastal sediments - Guang‐Chao Zhuang; Qiao Liu; Lin Yuan; Bingzheng Wu; Xiuqi Sui; Zhen Zhou; Jinyan Wang; Liang Dong; Xiting Liu; Gui‐Peng Yang; Fengping Wang (Limnology and Oceanography, 2026)
Methylotrophic methanogenesis has recently been recognized as a key process driving cryptic methane cycling within sulfate‐reducing sediments. Here we conducted biogeochemical analyses of methanogenic substrates, activity, and communities in two sediment cores (4–5 m) from the East China Sea, to constrain the dynamics and controls of methylotrophic methanogenesis in coastal sediments. We detected micromolar concentrations of methane in the presence of sulfate and high methane concentrations (up to 4.2 mM) below the sulfate–methane transition zone (~ 150–170 cm). Stable isotope composition of methane was strongly depleted (−77‰ to −91‰), indicating its biological production. Methanogenic substrates including H 2 /CO 2 , acetate, and methylated compounds were detected in the porewaters and/or sediments. Radiotracer experiments indicated methane production from various substrates, and the presence of sulfate did not inhibit methanogenesis at either site. At the coastal site with the dominance of marine organic matter (total organic carbon: 0.6%; C/N ratio: ~ 6.4; δ 13 C‐total organic carbon: −22‰), methane was primarily produced from hydrogenotrophic methanogenesis, consistent with the progressive enrichment of 13 C in dissolved inorganic carbon with depth below the sulfate–methane transition zone. However, methylotrophic methanogenesis from methanol and trimethylamine contributed significantly to methane production (up to 30.2%) at the estuarine site (total organic carbon: 0.5%; C/N ratio: 7.4, δ 13 C‐total organic carbon: −23‰) with elevated terrestrial organic matter input, also reflected from the predominance of long chain odd carbon n‐alkanes. These findings suggested that organic carbon source and composition, instead of sulfate, control methanogenic activity, providing evidence that high terrestrial organic inputs could significantly enhance methylotrophic methanogenesis in coastal sediments.

Differential life cycle toxic effects and molecular mechanisms of Di(2-ethylhexyl) phthalate (DEHP) exposure on the female reproductive system - Kangshuai Zhang; Yuxuan Lin; Xiance Sun; Cong Zhang; Haoyuan Deng; Xiaofeng Yao; Ningning Wang; Guang Yang (Toxicology, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

The effects of active surface morphing on the propulsive performance and acoustic characteristics of a flapping foil - Chun-yu Guo; Lei Jin; Guang-yu Shi; Lin Cai; Lu-cheng Sun; Yi-jie Sun (Ocean Engineering, 2025)

Frequency-domain linear potential analysis on the near-trapping of water waves in the square cylinder array - Ying-Chao Ma; Hao Shen; Zhi-Wei Song; Hui Yang; Hong-Fei Mao; Zhong-Bing Zhou; Guang-Lin Wu (Ocean Engineering, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Paired lithium and barium isotopes uncover weathering and productivity controls on the late cambrian SPICE event - Jianlin Zhou; Feifei Zhang; Yi-Bo Lin; Guangying Ren; Guang-Yi Wei; Aihua Yang; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Deep learning-assisted bionic gustatory sensing system based on aggregate-tuned silver nanoclusters and functionalized MXene for multiple foodborne pathogens recognition - Yuandong Lin; Wei Xiang; Fengqi Wang; Yong-Guang Jia; Jingzhu Wu; Jun-Hu Cheng (Chemical Engineering Journal, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Metabolomics Reveals Reasons for the Efficacy of Acupuncture in Migraine Patients: The Role of Anaerobic Glycolysis and Mitochondrial Citrate in Migraine Relief - Zishan Gao; Xianzhong Yan; Rui Wang-Sattler; Marcela Covic; Guang Yu; Feifei Ge; Jia Lin; Qin Chen; Juan Liu; Sapna Sharma; Sophie Molnos; Brigitte Kuehnel; et al. (Phenomics, 2025)
Acupuncture is used worldwide to treat migraine, but its scientific mechanism remains unclear. Here, we report a 1 H NMR metabolomics study involving 40 migraine patients and 10 healthy individuals randomly receiving acupuncture or sham acupuncture, followed by machine learning techniques and functional analysis. We found that acupuncture at acupoints particularly enhanced anaerobic glycolysis and modified mitochondrial function by adjusting the levels of plasma pyruvic acid ( p = 0.012), lactic acid ( p = 0.031) and citrate ( p = 0.00079) at a Bonferroni-corrected level of significance compared to the pre-treatment level of these three metabolites in migraine patients. Therefore, acupuncture supplies energy to migraine patients and relieves migraine attacks. In contrast, we observed that sham acupuncture may partially supply energy to migraine patients through lipid metabolism by changing the levels of plasma lipid ( p = 0.0012), glycerine ( p = 0.021), and pyruvic acid ( p = 0.047) at a Bonferroni-corrected level of significance. The functional network analysis further indicates this different way of supplying energy contributes to the different effects of acupuncture and sham acupuncture. Our findings reveal novel metabolic evidence for the specific effect of acupuncture in relation to sham acupuncture. This metabolic evidence could enlighten a brand new direction into acupuncture analgesia mechanism, which in turn would pose fresh challenges for future acupuncture research.

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Conditional probabilistic-based domain adaptation for cross-subject EEG-based emotion recognition - Shichao Cheng; Yifan Wang; Jiawei Mei; Guang Lin; Jianhai Zhang; Wanzeng Kong (Cognitive Neurodynamics, 2025)

Comparative study on feeding habits, gonadal development and muscle nutritional value in triploid hybrids derived from blunt snout bream (Megalobrama amblycephala, ♀) × topmouth culter (Culter alburnus, ♂) - Guang-hai Dong; Zheng-nan Liu; Song-lin Chen; Yahui Feng; Jie Chen; Guodong Zheng; Shuming Zou (Aquaculture International, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Concentration-dependent visual SO2 detection from trace to pure in a zirconium MOF - Guang-Rui Si; Xiang-Jing Kong; Lin-Hua Xie; You-Tuo Zhang; Tao He; Jian-Rong Li (Science Bulletin, 2025)

Evaluating impacts of hydrology and pollution loadings on low dissolved oxygen in an urbanized tidal river network using modeling and monitoring - Heng Zhang; Jiahuan Liu; Tong Li; Siyu Zhang; Zhongyuan Lin; Zhengbo Jia; Wenping Gong; Guang Zhang (Journal of Hydrology, 2025)

Long-term organic fertilization reduces cadmium bioavailability via enhanced binding to organic fractions and Fe-bearing minerals - Zhi-Lai Chi; Qiang-Long Hu; Lin Shi; Fu-Sheng Sun; Jun Wang; Guang-Hui Yu (Journal of Hazardous Materials, 2025)

Response of invasive Solidago canadensis to foliar application of natural herbicide and glyphosate - Muhammad Anas; Zhi-Yun Huang; HuAnHe Xiong; Muhammad Imran; Meng-Ting Yan; Qaiser Javed; Guang-Qian Ren; Shan-Shan Qi; Jian Li; Zhi-Cong Dai; Dao-Lin Du (Journal of Environmental Management, 2025)

Closing in on carbonate uranium isotopes as a paleo-redox proxy based on continuous records from Late Oligocene to Holocene island carbonates - Guolin Xiong; Feifei Zhang; Yi-Bo Lin; Guang-Yi Wei; Na Li; Mengchun Cao; Xuexue Jia; Jian Wang; Wen Yan; Hai Cheng; Shu-zhong Shen (Geochimica et Cosmochimica Acta, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Establishment of succinic acid production in recombinant Kluyveromyces marxianus enhanced by AI-guided enzyme specificity engineering and redox-controlled fermentation optimization - Du-Wen Zeng; Yi-Fan Zhu; Yuan-Hong Jiang; Ya-Hao Ding; Zhen-Zhi Wang; Kai Li; Sha Liao; Ya-Chao Fan; Lin Zhang; Yu Guang Wang; Xin-Qing Zhao (Chemical Engineering Journal, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Biotransformation of oleanonic acid by circinella muscae to produce novel 11,12-epoxy-13,28-lactonized derivatives and their anti-neuroinflammatory activity - Wei Liu; Li Yang; Liu-Tong Guan; Jia-Hui Wang; Yao-Yu Liu; Yan Song; Jian-Lin Li; Wen-Li Wang; Bo-Yi Fan; Guang-Tong Chen (Natural Product Research, 2025)

Closing the oceanic lithium budget by continental shelf sediment removal - Qingquan Hong; Guang-Yi Wei; Gaojun Li; Yi-Bo Lin; Feifei Zhang; Shilei Li; Chenglong Wang; Zhimian Cao; Pinghe Cai; Tianyu Chen (Earth and Planetary Science Letters, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Antimicrobial activity and preservation efficiency of TEMPO-oxidized chitin/5-aminolevulinic acid films mediated by photodynamic inactivation against salmon fillets - Huajian Ou; Lu Chen; Qiaohui Zeng; Wangsheng Qiu; Zihao Lin; Konglong Feng; Guang Liu; Ping Qi; Weijuan Huang; Jing Jing Wang (Food Packaging and Shelf Life, 2025)

Estimation of surface duct parameters using AIS data based on Bayesian inversion method - Hong-Guang Wang; Li-Jun Zhang; Jie Han; Li-Feng Huang; Qing-Lin Zhu (Frontiers in Marine Science, 2025)
Automatic Identification System (AIS) operates within a very high frequency (VHF) maritime mobile band, which could be impacted by surface duct seriously. Utilizing AIS signals for atmospheric duct inversion is a relatively new technique in passive remote sensing. This study employs the Bayesian method to conduct inversion of maritime surface ducts based on AIS signals, categorizing surface ducts into surface-based and elevated-surface ducts. Initially, preliminary data on surface-based duct and elevated-surface duct parameters are acquired from historical sounding data, followed by correlation analysis and probability density distribution fitting of these surface duct parameters. Subsequently, the inversion method steps are provided, and using the same measured AIS data, the likelihood function and posterior probability are calculated by directly employing historical samples and samples generated using Latin Hypercube Sampling (LHS), to accomplish the estimation of surface duct parameters. Directly utilizing historical samples and LHS-generated samples for Bayesian inversion can consistently and accurately yield results with an elevated-surface duct, with the latter being slightly more accurate than the former. The root mean square errors for the AIS path loss, calculated using the inverted elevated-surface duct parameters, are 5.9 dB and 4.4 dB when compared with the measured data. In contrast, the error calculated from the inverted surface-based duct parameters is 21.9 dB.

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Harmonizing stakeholder interests in urban renewal: A novel planning approach using explainable machine learning and spatial optimization - Chuan Lin; Yilun Liu; Zhongyou Yuan; Hongmei Wang; Guang Li; Zegen Zhou; Han Wang; Xinyue An (Land Use Policy, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Soil comammox Nitrospira dominates over ammonia-oxidizing archaea and bacteria in the invasion of Solidago canadensis - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Xiang-Zhen Li; Dao-Lin Du; Zhi-Cong Dai; Guang-Qian Ren; Xiao-Jun Zheng; Chao-Ying Liu (Plant and Soil, 2025)

Development and validation of a Geospatial eXplainable Artificial Intelligence (GeoXAI) framework for mapping mosquito density in metropolitans - Xu Guang; Lanbin Xiang; Yifei He; Ning Zhang; Junyao Zheng; Yanmin Qin; Dongfeng Kong; Haidong Wang; Liangqiang Lin; Bin Zhu (Applied Geography, 2025)

Identification of gut microbiota causally associated with aging and longevity and mediation roles of the cerebrospinal fluid proteins: proteomic genetic evidence from Mendelian randomization - Ruonan Liu; Zheng Zhu; Yuanyue Zhu; Xin Lin; Hongjie Li; Tiange Wang; Jie Zheng; Mian Li; Zhiyun Zhao; Yu Xu; Jieli Lu; Weiqing Wang; et al. (GeroScience, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Calcium oxide modification of phosphorus migration pathways during hydrogen reduction of high-phosphorus limonite - Lian-da Zhao; Mei-lin Shi; Xing-jian Deng; Jing-song Wang; Guang Wang; Qing-guo Xue; Hai-bin Zuo; Xue-feng She (Process Safety and Environmental Protection, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Axial compressive performance of reinforced sea-sand concrete-filled square stainless steel tubular stub columns - Zhi-Bin Wang; Jing-Dong Tong; Chun-Guang Zhao; Ee Loon Tan; Xin Yu; Ji-Ting Lin (Engineering Structures, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

The landscape of cell lineage tracing - Ye Feng; Guang Liu; Haiqing Li; Lin Cheng (Science China Life Sciences, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

The stability of plant richness, composition, and cover responds nonlinearly to warming in a decade‐long experiment - Ruonan Shen; Yangjian Zhang; Juntao Zhu; Yunlong He; Zhoutao Zheng; Guang Zhao; Nan Cong; Bo Zhao; Xianzhou Zhang; Lin Jiang; Yann Hautier (Ecology, 2025)
Global warming is expected to change the diversity, composition, and functioning of plant communities. However, it remains unclear how warming alters the temporal stability of different aspects of plant communities and the extent to which these different aspects are interlinked or respond differently to warming. Here, using data from a 10‐year, multi‐level warming experiment in an alpine grassland, we quantified the temporal stability of three plant community aspects—species richness, composition, and cover—in response to warming scenarios that increase soil temperature by 0.4, 1.6, 2.1, and 2.5°C. We found a nonlinear concave stability response to warming for each of the three community aspects investigated. That is, moderate warming caused moderate increases in the stability of richness, composition, and cover, whereas severe warming caused strong decreases in stability. Additionally, we found that the processes contributing to stability differed among the three community aspects, with warming weakening the relationships between them. Severe warming reduced the stability of cover by reducing the stability of dominant species and species asynchrony. Compositional stability decreased due to declines in species richness, species asynchrony, and dominant species stability. Richness stability decreased due to a decline in species richness. Our results demonstrate that the stability of different community aspects responds nonlinearly to future warming scenarios, with moderate warming stabilizing but high‐level warming destabilizing plant species richness, composition, and cover. Our findings emphasize the collective influence of species richness, species asynchrony, and dominant species stability as key factors modulating community stability in the context of global warming.

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

Ran drives pancreatic cancer metastasis by activating the osteopontin-PI3K/AKT-androgen receptor signaling cascade - Lin Deng; Jingyi Ren; Dong Liu; Hong Li; Guang Yang; Kairui Wang; Yang Song; Haichuan Su (Toxicology and Applied Pharmacology, 2025)

Konjac glucomannan/ carboxylated cellulose nanofiber-based edible coating with tannic acid maintains quality and prolongs shelf-life of mango fruit - Jiaxin Wang; Mian Qin; Wei Wang; Yining Xia; Guang Wu; Hao Deng; Qiong Lin (Food Chemistry, 2025)

Harnessing microalgae: Pioneering strategies for cost-effective EPA synthesis - Yi-Ting Shen; Zi-Xu Zhang; Xin Qi; Hong-Xuan Wu; Yan-Cheng Lin; Wang Ma; Guang Yang; Xiao-Man Sun (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Carnosol mitigates Ang II-stimulated vascular injury and oxidative stress by directly binding to FAK and inhibiting its activation - Yucheng Jiang; Zhaozheng Zheng; JunYi Wang; Yingjie Liao; Zhihan Jia; Wante Lin; Diyun Xu; Jiong Wang; Gaojun Wu; Guang Liang; Bozhi Ye (Inflammopharmacology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Thermal processing and combustion characteristics of multi-component solid waste in coal-fired boilers - Guang Sun; Lin Li; Dennis Lu; Hui Wang; Lunbo Duan (Fuel, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Altered 3D genome reorganization mediates precocious myeloid differentiation of aged hematopoietic stem cells in inflammation - Xinyu Cui; Yu Dong; Qiang Zhan; Yixin Huang; Qianshu Zhu; Zihao Zhang; Guang Yang; Liping Wang; Shijun Shen; Jia Zhao; Zhiyi Lin; Jiatong Sun; et al. (Science China Life Sciences, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Differential responses of an economically important macroalga and a bloom-forming microalga to marine heatwaves in a coculture system - Xin Zhao; Lin Gao; Xu Li; Gang Li; Guang Gao (Aquaculture, 2025)

Greenspace and respiratory diseases and symptoms in Chinese children: A large-scale study exploring joint associations with ozone - Pei-Pei Dong; Gongbo Chen; Yue Wen; Joachim Heinrich; Elaine Fuertes; Tianyu Zhao; Nur Sabrina Idrose; Li-Zi Lin; Zhao-Huan Gui; Xiaodi Qin; Hongwei Tu; Guang-Hui Dong (Sustainable Cities and Society, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

SuperDecode: An integrated toolkit for analyzing mutations induced by genome editing - Fuquan Li; Xiyu Tan; Shengting Li; Shaotong Chen; Lin Liu; Jingjing Huang; Gufeng Li; Zijun Lu; Jinwen Wu; Dongchang Zeng; Yanqiu Luo; Xiaoou Dong; et al. (Molecular Plant, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Research progress on the environmental risk assessment and remediation technologies of heavy metal pollution in agricultural soil - Xurui Mai; Jing Tang; Juexuan Tang; Xinyue Zhu; Zhenhao Yang; Xi Liu; Xiaojie Zhuang; Guang Feng; Lin Tang (Journal of Environmental Sciences, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Influence of oxygen carrier on NOx and N2O emissions in biomass combustion within fluidized beds - Guang Sun; Lin Li; Dennis Lu; Ming Hu; Zhenkun Sun; Rongtao Wang; Yuqing Chen; Lunbo Duan (Process Safety and Environmental Protection, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Application of multiple-centers ESR dating to middle Pleistocene fluviolacustrine sediments and insights into the dose underestimation from the Ti–H center at high equivalent doses - Xingshuo Xu; Chuanyi Wei; Gongming Yin; Hao Ji; Chunru Liu; Lin Zhao; Huili Yang; Guang Yang (Quaternary Geochronology, 2024)

Cinnamic acid application inhibits the browning of cold-stored taro slices by maintaining membrane function, reducing flavonoid biosynthesis and enhancing glutathione metabolism - Yukun Wang; Hong Ye; Wei Lin; Guang Wang; Tao Luo; Jinming He; Bin Wang (Postharvest Biology and Technology, 2024)

Excellent antibiotic degradation through PMS activation via bio derived Fe-Mn oxides with tunable defect concentration: Synergy between singlet oxygen oxidation and electron transfer - Kai Teng; Jiajie Wu; Yuxi Chen; Lin Ge; Guang Li; Yuning Fan; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2024)

Environmental DNA reveals the spatiotemporal distribution and migration characteristics of the Yangtze finless porpoise, the sole aquatic mammal in the Yangtze River - Qiao Qiao; Quan Zhou; Jie Wang; Hao-jie Lin; Bo-yang Li; Hao Du; Zhen-guang Yan (Environmental Research, 2024)

Research on the mechanism of hydrogen production by catalytic fast co-pyrolysis of cotton stalks and polypropylene: An experimental and theoretical study - Lin Li; Langqi Shi; Zijun Zhang; Guang Sun; Zhaoying Li (Biomass and Bioenergy, 2024)

Sexual size dimorphism affecting mate choice and reproduction in the pine sawyer beetle, Monochamus alternatus - Guang-Nan Zheng; Xiong Z. He; Xiao-Yun Wang; Xia-Lin Zheng (Oecologia, 2024)

Genome-Based Classification of ‘Haloarcula aidinensis’ and Description of Three Novel Halophilic Archaea Isolated from an Inland Saline Lake, Coastal Saline Soil, and a Marine Solar Saltern - Xue Ma; Yao Hu; Jing Hou; Yu-Guang Zhou; Heng-Lin Cui (Current Microbiology, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Prediction of carbonate permeability from multi-resolution CT scans and deep learning - Lin Zhang; Guang-dong Chen; Jing Ba; José M. Carcione; Wen-hao Xu; Zhi-jian Fang (Applied Geophysics, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Barium isotopes constrain the triggering mechanism of the Cretaceous OAE 2 in the Neotethys Ocean - Feifei Zhang; Guolin Xiong; Guang-Yi Wei; Yi-Bo Lin; Xianghui Li; Shu-zhong Shen (Earth and Planetary Science Letters, 2024)

A Cohesive Model-Based Nonlinear Discontinuous Deformation Analysis for Tensile Fracture in Geotechnical Materials - Shi-Lin Gong; Cheng-Bao Hu; Dao-Sheng Ling; Jia-Ying Liu; Zhong-Ling Zong; Guang-Qi Chen; Miao-Miao Sun (Rock Mechanics and Rock Engineering, 2024)

Study on Influence of Preset Circular Holes on Propagation of Blast-Induced Cracks Based on Experiments and Discrete Element Simulations - Minghua Lin; Baiquan Lin; Wei Yang; Ting Liu; Yang Shen; Tong Liu; Xiangliang Zhang; Fei Lin; Guang Xia (Rock Mechanics and Rock Engineering, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Marine heatwaves alter competition between the cultured macroalga Gracilariopsis lemaneiformis and the harmful bloom alga Skeletonema costatum - Lin Gao; Yonglong Xiong; Fei-Xue Fu; David A. Hutchins; Kunshan Gao; Guang Gao (Science of The Total Environment, 2024)

New insight into the exotic states strongly coupled with the D D ‾ ∗ from the T cc + - Guang-Juan Wang; Zhi Yang; Jia-Jun Wu; Makoto Oka; Shi-Lin Zhu (Science Bulletin, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

The effects of online-training artificial neural network mechanism and multi-stage parametric modeling method on simulation-based design system for ship optimization - Lin Du; Qin Wu; Yuehui Shu; Guang-nian Li (Ocean Engineering, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Assessment of chlorine and hydrogen peroxide on airborne bacteria: Disinfection efficiency and induction of antibiotic resistance - Siyi Wang; Zhiwei Shao; Guang Chen; Bingjie Lin; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Sustainable strategies for recovering metallic copper from waste printed circuit boards: Clean leaching and micro-nano copper powder preparation - Xi-guang Li; Shun-xiang Shi; Shuai Yan; Lin Li; Xi-zhuang Qin; Xiang-nan Zhu (Journal of Environmental Chemical Engineering, 2024)

Enhanced adsorption of trace carbon dioxide from acetylene using Polyethyleneimine-Diethanolamine blends - Jiajin Huang; Yongsheng Huang; Danxia Lin; Liang Yu; Guang Miao; Mengxuan Cao; Xingbei Wu; Hao Wang; Qibin Xia (Chemical Engineering Journal, 2024)

A novel explainable kinetic model for two-stage fermentation profile - Xiao-Yan Huang; Chen-Guang Liu; Yen-Han Lin (Chemical Engineering Journal, 2024)

Online monitoring lignocellulosic particles by focus beam reflectance measurement for efficient bioprocessing - Ji-Wen Yao; Xiao-Yan Huang; Yen-Han Lin; Chen-Guang Liu; Feng-Wu Bai (Bioresource Technology, 2024)

Prognostic model incorporating immune checkpoint genes to predict the immunotherapy efficacy for lung adenocarcinoma: a cohort study integrating machine learning algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Guang-Yu Wang; Fu-Quan Zhang (Immunologic Research, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

Systematic Mendelian Randomization Exploring Druggable Genes for Hemorrhagic Strokes - Lun-Zhe Yang; Yong Yang; Chuan Hong; Qi-Zhe Wu; Xiong-Jie Shi; Yi-Lin Liu; Guang-Zhong Chen (Molecular Neurobiology, 2024)
Patients with hemorrhagic stroke have high rates of morbidity and mortality, and drugs for prevention are very limited. Mendelian randomization (MR) analysis can increase the success rate of drug development by providing genetic evidence. Previous MR analyses only analyzed the role of individual drug target genes in hemorrhagic stroke; therefore, we used MR analysis to systematically explore the druggable genes for hemorrhagic stroke. We sequentially performed summary-data-based MR analysis and two-sample MR analysis to assess the associations of all genes within the database with intracranial aneurysm, intracerebral hemorrhage, and their subtypes. Validated genes were further analyzed by colocalization. Only genes that were positive in all three analyses and were druggable were considered desirable genes. We also explored the mediators of genes affecting hemorrhagic stroke incidence. Finally, the associations of druggable genes with other cardiovascular diseases were analyzed to assess potential side effects. We identified 56 genes that significantly affected hemorrhagic stroke incidence. Moreover, TNFSF12 , SLC22A4 , SPARC , KL , RELT , and ADORA3 were found to be druggable. The inhibition of TNFSF12 , SLC22A4 , and SPARC can reduce the risk of intracranial aneurysm, subarachnoid hemorrhage, and intracerebral hemorrhage. Gene-induced hypertension may be a potential mechanism by which these genes cause hemorrhagic stroke. We also found that blocking these genes may cause side effects, such as ischemic stroke and its subtypes. Our study revealed that six druggable genes were associated with hemorrhagic stroke, and the inhibition of TNFSF12 , SLC22A4 , and SPARC had preventive effects against hemorrhagic strokes. Graphical Abstract

Two new aryltetralin-type lignans from Camellia oleifera husk - Huai-yu Cheng; Tian-qi Xu; Ya-lin Hu; Qing Shu; Wei Xu; Chun-lin Fan; Guang-xiong Zhou (Natural Product Research, 2024)

Flexible self-powered bioelectronics enables personalized health management from diagnosis to therapy - Guang Yao; Xingyi Gan; Yuan Lin (Science Bulletin, 2024)

Electrospun multi-functional medicated tri-section Janus nanofibers for an improved anti-adhesion tendon repair - Lin Xu; Qisheng Li; Haibing Wang; Hui Liu; Deng-Guang Yu; Sim-Wan Annie Bligh; Xuhua Lu (Chemical Engineering Journal, 2024)

Preparation of a long-term mildew resistant and strong soy protein adhesive via constructing multiple crosslinking networks - Yanqiu Chen; Xinxin Huang; Guang Wang; Hanbing Liu; Xixiang Lin; Pingan Song; Wenrui Zhou; Jianlin Luo; Qiang Gao (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Implementation of Viscoelastic Artificial Boundary and Seismic Motion Input Method in Three-Dimensional Discontinuous Deformation Analysis Method - Si-huang Lin; Tao Deng; Lu Zheng; Hong Zhang; Wei Wu; Xiao-dong Fu; Guang-qi Chen (Rock Mechanics and Rock Engineering, 2024)

The Association Between Dietary Magnesium Intake with Chronic Obstructive Pulmonary Disease and Lung Function in US Population: a Cross-sectional Study - Zhi-Feng Lin; Hua-Wei Lin; Wan-Zhe Liao; Ze-Min Huang; Xiao-Yue Liao; Yi-Yao Wang; Xu-Guang Guo (Biological Trace Element Research, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Biochar with enhanced performance prepared based on “graphite-structure regulation” conjecture designed to effectively control water pollution - Bolun Zhang; Yiping Jin; Jiacheng Lin; Ziyu Guo; Guang Chen; Yingjie Su; Xiaoxiao Yu; Shanshan Tang; Siji Chen; Jian Li (Science of The Total Environment, 2024)

Genome-wide identification of G-protein coupled receptors (GPCRs) and their expression profile in response to β-cypermethrin stress in Zeugodacus cucurbitae - Samina Shabbir; Ming-guang Deng; Mohsin Nawaz; Qing-sheng Lin (Pesticide Biochemistry and Physiology, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Constructing gradient porosity beyond sieving-kinetics trade-off: Rapidly precise CO2/CH4 separation on carbon nanofibers - Jiawu Huang; Cuiting Yang; Shengjun Du; Lin Zhu; Zhenglin Du; Guang Miao; Chunshan Song; Jing Xiao (Chemical Engineering Journal, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Biochar with improved performance prepared based on “micro-explosive reaction” conjecture for effective removal of antibiotics - Yiping Jin; Bolun Zhang; Ziyu Guo; Jiacheng Lin; Guang Chen; Siji Chen; Yingjie Su (Fuel, 2024)

Barium isotopes in stromatolites through deep-time: A novel tracer for metal cycling in the photic zone - Simon V. Hohl; Yi-Bo Lin; Hai-Zhen Wei; Guang-Yi Wei; Sebastian Viehmann (Earth and Planetary Science Letters, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Simultaneous determination of seawater trimethylamine and methanol by purge and trap gas chromatography using dual nitrogen-phosphorus detector and flame-ionization detector - Fei Jiang; Zhen Zhou; Jin-Yan Wang; Wen-Jia Guan; Lei-Gang Han; Xian-Biao Lin; Guang-Chao Zhuang (Frontiers in Marine Science, 2024)
Compounds containing one carbon atom or no carbon-carbon bond (C1 compounds), such as trimethylamine and methanol, are important climate relevant gases in the atmosphere and play key roles in global warming. The ocean is a significant source or sink of such compounds, while the concentrations of trimethylamine and methanol in seawater remain largely unconstrained due to the analytical challenges involved. Therefore, it is necessary to establish a continuous, rapid and sensitive method for the determination of these compounds with high polarity, volatility or solubility at low seawater concentrations. Here we developed a purge and trap system, coupled to a gas chromatography equipped with dual nitrogen phosphorus detector (NPD) and flame ionization detector (FID) for the simultaneous online analysis of trimethylamine and methanol at nanomolar range using a small sample volume (~ 10 mL). The dual detection of trimethylamine and methanol with NPD or FID was achieved by installing a capillary flow splitter between the capillary column and detectors. After modification and optimization of the setup and conditions, excellent linearity (R 2 > 0.99) and repeatability (< 6%) were obtained for both compounds; the detection limits for trimethylamine and methanol were 0.3 nM and 17.6 nM, respectively. Using this method, water samples collected from coastal and open ocean were analyzed; trimethylamine and methanol concentrations ranged from 0.6 to 18.8 nM and 26.0 to 256.2 nM, respectively. Collectively, this method allowed for online, rapid, sensitive and simultaneous quantification of trace trimethylamine and methanol concentrations with low-cost instrumentation and small sample volume, which makes it promising for further application in volatile compounds analysis in marine environments.

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Research on the influence of parallel joints on the extension length and morphology of blasting cracks - Yang Shen; Baiquan Lin; Ting Liu; Minghua Lin; Tong Liu; Wei Yang; Fei Lin; Guang Xia (Computers and Geotechnics, 2024)

Enlightening thermoelectric mastery: Bio-inspired cellulose gel containing eco-friendly deep eutectic solvents - Yuxi Chen; Gonghua Hong; Lei Li; Qing Qu; Guang Li; Jiajie Wu; Lin Ge (Chemical Engineering Journal, 2024)

Salt intrusion dynamics in a well-mixed sub-estuary connected to a partially to well-mixed main estuary - Zhongyuan Lin; Guang Zhang; Huazhi Zou; Wenping Gong (Ocean Science, 2024)
Salt intrusion in estuaries has been exacerbated by climate change and human activities. Previous studies have primarily focused on salt intrusion in the mainstem of estuaries, whereas those in sub-estuaries (those that branch off their main estuaries) have received less attention. During an extended La Niña event from 2021 to 2022, a sub-estuary (the East River estuary) alongside the Pearl River estuary, China, experienced severe salt intrusions, posing a threat to the freshwater supply in the surrounding area. Observations revealed that maximum salinities in the main estuary typically preceded spring tides, exhibiting significant asymmetry in salinity rise and fall over a fortnightly timescale. In contrast, in the upstream region of the sub-estuary, the variation in salinity was in phase with that of the tidal range, and the rise and fall of the salinity were more symmetrical. Inspired by these observations, we employed idealized numerical models and analytical solutions to investigate the underlying physics behind these behaviors. It was discovered that under normal dry conditions (with a river discharge of 1500 m3 s−1 at the head of the main estuary), the river–tide interaction and change in horizontal dispersion accounted for the in-phase relationship between the salinity and tidal range in the upstream region of the sub-estuary. Under extremely dry conditions (i.e., a river discharge of 500 m3 s−1 at the head of the main estuary), salinity variations were in phase with those of the tidal range in the middle as well as the upstream region of the sub-estuary. The variation in salinity in the main estuary along with those in salt dispersion and freshwater influx inside the sub-estuary collectively influenced salinity variation in the well-mixed sub-estuary. These findings have important implications for water resource management and salt intrusion prevention in the catchment area.

Mono-2-ethylhexylphthalate (MEHP) is a potent agonist of human TRPA1 channel - Megan Goh; Lin Fu; Wei-Guang Seetoh; Ann Koay; Huang Hua; Shi Min Tan; Shermaine Huiping Tay; Elaine Chin Jinfeng; Nimo Abdullah; Shi Yan Ng; Manikandan Lakshmanan; Prakash Arumugam (Chemosphere, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Fucoidan-based antibody-free magnetic nanoparticle for on-site detection of waterborne SARS-CoV-2 - Jinhui Zhu; Huijun Lu; Qiuyuan Lin; Tong Zhang; Guang Chen; Yang Zhou; Guodong Sui (Science of The Total Environment, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Numerical investigation of water entry characteristics of a projectile in the wave environment - Chen Wang; Qiaogao Huang; Lin Lu; Guang Pan; Shan Gao (Ocean Engineering, 2024)

Estimates of chlorine isotope fractionation factors using density functional theory: Applications to ore-forming systems - Miao-Miao Zhang; Hai-Zhen Wei; Jian-Jun Lu; A.E. Williams-Jones; C.J. Eastoe; Wei-Qiang Li; Zhi-Guang Xia; S.V. Hohl; Jing Ma; Yue Cai; Shao-Yong Jiang; Jun-Lin Wang (Geochimica et Cosmochimica Acta, 2024)

Diagenetic effects on strontium isotopes in shallow-water carbonate sediments from Middle Miocene to Recent - Xinran Chen; Mengchun Cao; Thomas J. Algeo; Na Li; Guang-yi Wei; Yi-bo Lin; Hua Zhang; Lei Xiang; Youhua Zhu; Changgui Xu; Caiwei Fan; Shuzhong Shen; et al. (Chemical Geology, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

Prolonged Exposure to Plant Volatiles does not Significantly Affect Pban Expression and Mating Behavior in Diamondback Moth [Plutella Xylostella (Lepidoptera: Plutellidae)] - Houjun Tian; Ruibin Xu; Heng Li; Shuo Lin; Yixin Chen; Yong Chen; Guang Yang; Hui Wei (Journal of Chemical Ecology, 2024)

Nitrogen availability regulates the effects of a simulated marine heatwave on carbon sequestration and phycosphere bacteria of a marine crop - Meijia Jiang; Jason M. Hall‐Spencer; Lin Gao; Zengling Ma; Guang Gao (Limnology and Oceanography, 2024)
Great hope has been pinned on seaweed cultivation as being a potent way of removing CO 2 to reduce rates of sea surface warming and acidification. Marine heatwaves and nitrogen pollution in coastal ecosystems are serious current issues that need to be better understood to inform decision making and policy. Here, we investigated the effects of a simulated heatwave and nitrogen pollution on carbon sequestration by an important seaweed crop species and its phycosphere bacteria. Gracilaria lemaneiformis was grown in ambient and high nitrogen conditions (14 and 200 μ M L −1 ). Photosynthetic rate, seaweed biomass and particulate organic carbon accumulation were significantly increased in “high nitrogen‐no heatwave” conditions. In “ambient nitrogen heatwave” conditions, the expression of genes related to photosynthesis was down regulated and the seaweeds lost more dissolved organic carbon (DOC) to the surrounding water, resulting in more refractory dissolved organic carbon (RDOC). In “high nitrogen heatwave” conditions, photosynthetic gene expression was upregulated; bacterial abundance was also increased that can explain the reduced DOC and RDOC accumulation. The simulated heatwave reduced bacterial diversity while high nitrogen alleviated this effect. These findings suggest that the economically important alga G . lemaneiformis may lose more DOC and RDOC to nearshore waters during marine heatwave events, enhancing carbon sequestration, while nitrogen enrichment has a counteractive effect.

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

Nitric oxide regulates the lignification and carotenoid biosynthesis of postharvest carrot (Daucus carota L.) - Miao Sun; Tao Yang; Xuan-Huan Qiao; Peng Zhao; Zhi-Peng Zhu; Guang-Long Wang; Lin-Lin Xu; Ai-Sheng Xiong (Postharvest Biology and Technology, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Evaluation storage capacity of six kind late-maturing Actinidia arguta resources - Jiabao Wang; Guanlin Qian; Song Pan; Tiancheng Ye; Miao Yan; Xiaoman Liang; Lin Hui; Xina Cong; Ruiyu Yang; Heran Xu; Guang Xin (Journal of Stored Products Research, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Hierarchical Y zeolite with accessible intracrystalline mesopores and enhanced hydrocracking performances via sequential multi-carboxyl acid and fluoroborate post-treatments - Lin-Jiao Wei; Peng Peng; Ke Qiao; Guang-Nan Cheng; Ubong Jerome Etim; Zi-Feng Yan (Fuel, 2023)

Widespread clay authigenesis and highly congruent silicate weathering in the Marinoan aftermath - Yi-Sheng Yin; Guang-Yi Wei; Philip A.E. Pogge von Strandmann; Maxwell A. Lechte; Simon V. Hohl; Yi-Bo Lin; Da Li; Tianyu Chen; Tao Yang; Feifei Zhang; Terry T. Isson; He Zhang; et al. (Earth and Planetary Science Letters, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Traditional Chinese medicine bufalin inhibits infectious pancreatic necrosis virus genogroups I and V infection in vitro and in vivo - Jing-Zhuang Zhao; Lin-Fang Li; Li-Ming Xu; Yi-Zhi Shao; Guang-Ming Ren; Qi Liu; Tong-Yan Lu (Aquaculture, 2023)

Residues of sulfoxaflor and its metabolites in floral and extrafloral nectar from Hibiscus rosa-sinensis L. (Malvaceae) with or without co-application of tebuconazole - Hong-Xia Zhou; Man-Huan Cheng; Juan-Lin Pan; Peng Cui; Yue-Qin Song; Ying Yu; Jun Cao; Hong-Guang Zha (Pesticide Biochemistry and Physiology, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Utilization of lipidic food waste as low-cost nutrients for enhancing the potentiality of biofuel production from engineered diatom under temperature variations - Yu-Feng Yang; Guang-Bin Ye; Hua-Jun Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiao-Fei Zheng; Arivalagan Pugazhendhi; Xiang Wang (Bioresource Technology, 2023)

Effects of the core heading date genes Hd1, Ghd7, DTH8, and PRR37 on yield-related traits in rice - Kangli Sun; Wubei Zong; Dongdong Xiao; Zeqiang Wu; Xiaotong Guo; Fuquan Li; Yingang Song; Shengting Li; Guangliang Wei; Yu Hao; Bingqun Xu; Weitao Li; et al. (Theoretical and Applied Genetics, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chemical constituents from the leaves of Cinnamomum camphora and their α-glucosidase inhibitory activities - Xing Jiang; Xi-Han Zhang; Yu-Xin Li; Kai Chen; Bin Lin; Tian-Qi Lu; Min Yang; Guang-Tong Chen; Bo-Yi Fan; Wen-Li Wang (Phytochemistry Letters, 2023)

Two new sesquiterpenes from the aerial parts of Bixa orellana - Xia Zhang; Lei Huang; Qing Shu; Tian-Qi Xu; Yi-Min Chen; Ya-Lin Hu; Chun-Lin Fan; Xiao-Qi Zhang; Wen-Cai Ye; Guang-Xiong Zhou (Phytochemistry Letters, 2023)

Nonlinear energy sink-based study on vortex-induced vibration and control of foil-cylinder coupled structure - Dongyang Chen; Rui Xu; Yaochen Lin; Nansha Gao; Guang Pan; Marzocca Pier (Ocean Engineering, 2023)

Balanced nitrogen–iron sufficiency boosts grain yield and nitrogen use efficiency by promoting tillering - Ying Song; Guang-Yu Wan; Jing-Xian Wang; Zi-Sheng Zhang; Jin-Qiu Xia; Liang-Qi Sun; Jie Lu; Chuan-Xi Ma; Lin-Hui Yu; Cheng-Bin Xiang; Jie Wu (Molecular Plant, 2023)

Deep transfer learning based on transformer for flood forecasting in data-sparse basins - Yuanhao Xu; Kairong Lin; Caihong Hu; Shuli Wang; Qiang Wu; Li Zhang; Guang Ran (Journal of Hydrology, 2023)

Culturable and inhalable airborne bacteria in a semiunderground municipal wastewater treatment plant: Distribution, transmission, and health risk assessment - Xiang Zhang; Bingjie Lu; Guang Chen; Lihua Wang; Bingjie Lin; Zhengliang Peng; Songliu Lu; Dan Li; Jianmin Chen (Journal of Hazardous Materials, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Cheese-like Ti3C2 for enhanced hydrogen storage - Chen Gu; Hai-Guang Gao; Peng Tan; Ya-Na Liu; Xiao-Qin Liu; Xiao-Hui Hu; Yun-Feng Zhu; Lin-Bing Sun (Chemical Engineering Journal, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

Geochemical characteristics of the Chang 7 Member in the southwestern Ordos Basin, China: the influence of sedimentary environment on the organic matter enrichment - Chen Li; Shi-Jia Chen; Jian-Bo Liao; Yu-Ting Hou; Jian Yu; Guang-Lin Liu; Kun Xu; Xue-Ting Wu (Palaeoworld, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Phosphorylation modification orchestrates the functionalities of peroxin 14 in filamentous entomopathogenic fungus Beauveria bassiana - Hai-Yan Lin; Ming-Guang Feng; Sheng-Hua Ying (Fungal Biology, 2023)

Quantitative proteomics provides insights into the mechanism of the differences in heat-induced gel properties for egg white proteins with different interior quality during ageing in laying hens - Guang Li; Siyuan Mi; Qi Zeng; Lin Wang; Xingbo Liu; Ming Zhang; Zengpeng Lv; Yongguo Jin; Junyou Li; Yuming Guo; Bingkun Zhang (Food Chemistry, 2023)

Fluorinated carbonate-based electrolyte engineering solvation structure for high-voltage Li||LiNiO2 cell - Wei-Chen Zheng; Jin-Xia Lin; Hui Chen; Shi-Shi Liu; Chen-Guang Shi; Ling Huang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Four organosulfur compounds from the seeds of Capsella bursa-pastoris and their anti-inflammatory activities - Zhen-Zhen Wei; Ti-Qiang Zhou; Zi-Ming Xia; Si-Fan Liu; Min Li; Guang-Jie Zhang; Ying Tian; Bin Li; Lin Wang (Natural Product Research, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Mechanism of testicular injury induced by Di-ethylhexyl phthalate and its protective agents - Yuxuan Lin; Wenqi Xu; Ling Yang; Zhengguo Chen; Jianan Zhai; Qi zhu; Zhifang Guo; Ningning Wang; Cong Zhang; Haoyuan Deng; Shaopeng Wang; Guang Yang (Chemico-Biological Interactions, 2023)

Mixed exposure effect of seminal metals on semen quality, mediation of total antioxidant capacity, and moderation of GSTM1/GSTT1 gene deletion in Chinese reproductive-aged men - Jingchao Ren; Huidong Jin; Chen Zhang; Song Liu; Yufen Han; Jinyan Xi; Jinhu Cao; Fenglong Lin; Pingyang Zhang; Fengquan Zhang; Guang-hui Zhang; Huijun Yang; et al. (Environmental Research, 2023)

Metagenomic insights into the inhibitory mechanisms of Cu on fermentative hydrogen production - Jinman Cao; Guilan Duan; Aijun Lin; Yaoyu Zhou; Siming You; Jonathan W.C. Wong; Guang Yang (Bioresource Technology, 2023)

New dimeric sesquiterpenoids from the whole plant of Artemisia sieversiana - Jun-yi Dong; Yu-xing Cai; Ya-lin Li; Yu-xin Zhang; Zhan-peng Yu; Ling-yi Kong; Jian-guang Luo (Phytochemistry Letters, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Experimental study on coal combustion by using the ilmenite ore as active bed material in a 0.3 MWth circulating fluidized bed - Lin Li; Junhua Mao; Wu Tang; Guang Sun; Quanbin Gu; Xiaoyan Lu; Ke Shao; Yuqing Chen; Lunbo Duan (Fuel, 2023)

Different cold tolerances among three strains of large yellow croaker: related to antioxidant defense and energy metabolism - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Hui Zhang; Yu-Cong Huang; Wei-Guang Zou (Fish Physiology and Biochemistry, 2023)

Geostatistical inversion method based on seismic waveform similarity - Xue-Bin Ni; Jia-Jia Zhang; Kang Chen; Guang-Zhi Zhang; Bao-Li Wang; Zhuo-Fan Liu; Ying Lin (Applied Geophysics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Insufficient evidence to link human exposure to heavy metals with biomarkers of glioma - Meng-Yi Xie; Guang-Long Huang; Zhi-Ying Lin; Xiang-Fei Sun; Chen-Chou Wu; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

The eisosomes contribute to acid tolerance of yeast by maintaining cell membrane integrity - Chao Li; Jun Lu; Xue-Jiao Yan; Chang-Wen Li; Liang-Cai Lin; Dong-Guang Xiao; Cui-Ying Zhang (Food Microbiology, 2023)

Correction to: Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2023)

Ultrasensitive amperometric determination of hand, foot and mouth disease based on gold nanoflower modified microelectrode - Yu Zhong; Xiang-Guang Hu; Ai-Lin Liu; Yun Lei (Analytica Chimica Acta, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Experimental study on penetration characteristics of an open-ended pile under static and dynamic driving methods - Jingxue Lu; Hongfeng Guang; Lin Cui; Junwei Liu; Cheng Wang; Subramani Anandha Kumar (Soil Dynamics and Earthquake Engineering, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Optimal design of horizontal axis tidal current turbine blade - Zhen-qi Li; Guang-nian Li; Lin Du; Hai-peng Guo; Wen-xin Yuan (Ocean Engineering, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

Particle Collision Study Based on a Rotational Boundary Condition - Yi Li; Xiangyun Zhao; Zhe Lin; Guang Zhang (Journal of Marine Science and Engineering, 2023)
The main engineering machinery for the hydrodynamic lifting of seafloor mineral particles is rotor machinery with rotating impeller motion. It is important to study the rebound mechanism of collisions between particles and rotating walls to improve the accuracy of numerical simulation of rotor machinery. In this study, the law of motion change after collisions between particles and rotating walls is investigated using an experimental research method. The results show that the deflection angle of the particles after collision decreases with increases in the rotational speed of the wall, and the spin angular velocity increases with increases in the rotational speed of the wall. The normal velocity coefficient of restitution under the rotating wall is not affected by the rotational speed of the wall. The tangential coefficient of restitution under rotational boundary condition is smaller than the tangential coefficient of restitution under the stationary wall, and the higher the rotational speed, the closer it is to the coefficient of restitution under the stationary wall. During collision in the experiment, the main mode of contact between the particle and the rotating wall is sliding contact. Sliding friction between the particle and the rotating wall results in energy loss in the tangential velocity of the particle, and also provides energy for deflection of the particle’s trajectory and increased kinetic energy from the spin angular velocity; sliding friction loss is affected by the speed of the wall.

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Establishing a high-performance anti-fouling PEI-ZIF-PAA membrane with improved Lewis acid-base interactions and hydrophilicity - Zhang-Hong Wan; Jing Guan; Chun-Miao Zhang; Wen-Qing Fei; Lin Wang; Shu-Guang Wang; Xue-Fei Sun (Chemosphere, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Dosing with pyrite significantly increases anammox performance: Its role in the electron transfer enhancement and the functions of the Fe-N-S cycle - Fan Feng; Zhigong Liu; Xi Tang; Xing Wu; Caiyan Qu; Seow Wah How; Di Wu; Ruiyang Xiao; Chong-Jian Tang; Zhang Lin; Liyuan Chai; Guang-Hao Chen (Water Research, 2023)

Evaluation of visible spectroscopy and low-field nuclear magnetic resonance techniques for screening the presence of defects in broiler breast fillets - Bin Pang; Brian Bowker; Chang-Hu Xue; Yao-Guang Chang; Jian Zhang; Lin Gao; Hong Zhuang (Food Control, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

Bixasteroid, a new compound from the fruits of Bixa orellana and its anti-inflammatory activity - Yi-min Chen; Tian-qi Xu; Xiao-qi Zhang; Chun-lin Fan; Wen-cai Ye; Wei Xu; Guang-xiong Zhou (Natural Product Research, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Enhanced intrathalamic morphological connectivity in patients with chronic insomnia - Xi Ye; Yuping Yang; Guang Xu; Xinzhi Wang; Shiqi Lin; Xiaofen Ma (Brain Imaging and Behavior, 2023)

The onset process of the 2018/2019 Indonesian–Australian summer monsoon: The importance of the air–sea interaction - Yongliang Duan; Hongwei Liu; Ming Feng; Xiangzhou Song; Kuiping Li; Lin Liu; Baochao Liu; Guang Yang; Weidong Yu (Frontiers in Marine Science, 2023)
The Madden–Julian oscillation (MJO) and its associated air–sea interactions during the onset process of the 2018/2019 Indonesian–Australian summer monsoon (IASM) are investigated based on the in situ data from a moored buoy off the coast of northwest Australia, along with ERA5 reanalysis and satellite data. The results verify that the IASM onset in mid-December 2018 was triggered by the first-branch eastward-propagating MJO (FEMJO) originating from the tropical Indian Ocean. However, the strong negative SST anomaly (SSTA) was evident off northwest Australia, which weakens FEMJO over northern Australia and shifts the convective center further northward. The mixed layer heat budget analysis based on the buoy observations reveals that the increased latent heat loss that occurred before the arrival of the FEMJO convection was primarily attributed to the large air–sea temperature difference and strong winds, resulting in the pronounced SSTA.

The contribution of fish and seaweed mariculture to the coastal fluxes of biogenic elements in two important aquaculture areas, China - Yonglong Xiong; Lin Gao; Liyin Qu; Juntian Xu; Zengling Ma; Guang Gao (Science of The Total Environment, 2023)

Glioma is associated with exposure to legacy and alternative per- and polyfluoroalkyl substances - Meng-Yi Xie; Xiang-Fei Sun; Chen-Chou Wu; Guang-Long Huang; Po Wang; Zhi-Ying Lin; Ya-Wei Liu; Liang-Ying Liu; Eddy Y. Zeng (Journal of Hazardous Materials, 2023)

Bridging optical and SAR satellite image time series via contrastive feature extraction for crop classification - Yuan Yuan; Lei Lin; Zeng-Guang Zhou; Houjun Jiang; Qingshan Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Improved fuel conversion through oxygen carrier aided combustion during incineration of biomass-based solid waste in a rotary kiln - Xue Liu; Lunbo Duan; Yuanqiang Duan; Lin Li; Zhenkun Sun; Guang Sun (Fuel, 2023)

Screening of structural and functional alterations in duckweed (Lemna minor) induced by per- and polyfluoroalkyl substances (PFASs) with FTIR spectroscopy - Ying-Lin Wu; Qian Xiong; Ben Wang; You-Sheng Liu; Pei-Liang Zhou; Li-Xin Hu; Fang Liu; Guang-Guo Ying (Environmental Pollution, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Identification of the Hub Genes and the Signaling Pathways in Human iPSC-Cardiomyocytes Infected by SARS-CoV-2 - Li-Min Xie; Yin-Fei Huang; Ye-Ling Liu; Jia-Qi Liang; Wei Deng; Geng-Ling Lin; Huan-Min Luo; Xu-Guang Guo (Biochemical Genetics, 2022)

Study on the chemical composition of Caesalpinia sinensis - Lu-Fen Leng; Qi Lai; Dian Lv; Jun-Lin Yin; Guang-Zhi Zeng (Natural Product Research, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Functional characterization of two homologs of yeast acetyl-coenzyme A synthetase in the entomopathogenic fungus Beauveria bassiana - Jia-Hui Lei; Hai-Yan Lin; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2022)

Lignans and phenylpropanoids from the roots of Ficus hirta and their cytotoxic activities - Xian-Sheng Ye; Wen-Jing Tian; Xiang-Zhong Liu; Mi Zhou; De-Quan Zeng; Ting Lin; Guang-Hui Wang; Xin-Sheng Yao; Hai-Feng Chen (Natural Product Research, 2022)

Correction to: Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/ TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Fissistiganoids A and B: two new flavonoids from the Fissistigma tungfangense - Wan-Lin Zhong; Xue-Ming Zhou; Ji-Ling Yi; Xin-Ming Song; Bin Zhang; Jing-Yu Yang; Guang-Ying Chen (Natural Product Research, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Characterization of Joint Roughness Heterogeneity and Its Application in Representative Sample Investigations - Shi-Gui Du; Hang Lin; Rui Yong; Guang-Jian Liu (Rock Mechanics and Rock Engineering, 2022)
Rock joint surface roughness is usually characterized by heterogeneity, but the determination of a required number of samples for achieving a reasonable heterogeneity assessment remains a challenge. In this paper, a novel method, the global search method, was proposed to investigate the heterogeneity of rock joint roughness. In this method, the roughness heterogeneity was characterized based on a statistical analysis of the roughness of all samples extracted from different locations of a given rock joint. Analyses of the effective sample number were conducted, which showed that sampling bias was caused by an inadequate number of samples. To overcome this drawback, a large natural slate joint sample (1000 mm × 1000 mm in size) was digitized in a laboratory using a high-accuracy laser scanner. The roughness heterogeneities of both two-dimensional (2D) profiles and three-dimensional (3D) surface topographies were systematically investigated. The results show that the expected value obtained from conventional methods failed to accurately represent the overall roughness. The relative errors between the population parameter and the expected value varied not only from sample to sample but also with the scale. The roughness heterogeneity characteristics of joint samples of various sizes can be obtained using the global search method. This new method could facilitate the determination of the most representative samples and their positions.

New insights on Abelmoschus manihot flower development: dynamic changes of flavonoids based on a metabolomic approach - Jie Li; Guang-ying Ye; Hai-lin Liu; Zai-hua Wang (Journal of Plant Biochemistry and Biotechnology, 2022)

Efficient removal of pefloxacin from aqueous solution by acid–alkali modified sludge-based biochar: adsorption kinetics, isotherm, thermodynamics, and mechanism - Hongli Huang; Yongxin Zheng; Dongning Wei; Guang Yang; Xin Peng; Lingjia Fan; Lin Luo; Yaoyu Zhou (Environmental Science and Pollution Research, 2022)

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Comparative Transcriptomics of Gonads Reveals the Molecular Mechanisms Underlying Gonadal Development in Giant Freshwater Prawns (Macrobrachium rosenbergii) - Guang Yang; Zhendong Qin; Zhijie Lu; Rishen Liang; Lijuan Zhao; Gan Pan; Li Lin; Kai Zhang (Journal of Marine Science and Engineering, 2022)
The giant freshwater prawn, Macrobrachium rosenbergii, is a prawn that has economic significance throughout the world. It exhibits sex-related growth dimorphism, whereby the males grow significantly more rapidly than the females. Therefore, a study on the molecular regulatory mechanism, which underlies the sexual differentiation of M. rosenbergii, is of both scientific and commercial importance. However, a scarcity of genomic and transcriptomic resources severely limits our knowledge of the sexual differentiation mechanisms in M. rosenbergii. Here, transcriptome sequencing of several gonadic samples of males and females in M. rosenbergii was performed to investigate the molecular basis underlying gonadal development. Our results showed that 2149 unigenes presented as differentially expressed genes (DEGs) in the ovaries of females compared to the testes of males, which contained 484 down-regulated and 1665 up-regulated genes. Enrichment analysis of DEGs revealed many of these genes to be related to sexual differentiation and gonadal development. From our transcriptome analyses, and as confirmed by quantitative real-time PCR, male-related genes (Mrr, MRPINK, IR, IAGBP, TESK1, and dsx) in the testes were significantly up-regulated, and female-related genes (ERR, Sxl3, cyclinB, Dmrt99B, PPP2A, and ADCY9) in the ovaries were also significantly up-regulated. This indicates the potential role these genes play in the gonadal development of M. rosenbergii. Furthermore, multiple signal transduction pathways relating to gonadal maturation and spermatogenesis, including MAPK, were identified herein. Our data also supports previous ideas that IAG and IAGBP-IR signaling schemes could help in the regulation of testis’ development in M. rosenbergii and the ERR gene could regulate ovarian development by affecting the expression of cyclinB, PPP2A, and ADCY9. The data from this study provides incredibly usefully genomic resources for future research on the sexual differentiation and practical aquaculture of M. rosenbergii.

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Interleukin-13 Affects the Recovery Processes in a Mouse Model of Hemorrhagic Stroke with Bilateral Tibial Fracture - Ya’nan Yan; Cheng Gao; Guang Chen; Xueshi Chen; Yanglin Wu; Heng Xu; Zhiqi Cheng; Chengliang Luo; Mingyang Zhang; Tao Wang; Jun Lin; Xiping Chen; et al. (Molecular Neurobiology, 2022)

Special Issue: Geostatistics and Machine Learning - Sandra De Iaco; Dionissios T. Hristopulos; Guang Lin (Mathematical Geosciences, 2022)
Recent years have seen a steady growth in the number of papers that apply machine learning methods to problems in the earth sciences. Although they have different origins, machine learning and geostatistics share concepts and methods. For example, the kriging formalism can be cast in the machine learning framework of Gaussian process regression. Machine learning, with its focus on algorithms and ability to seek, identify, and exploit hidden structures in big data sets, is providing new tools for exploration and prediction in the earth sciences. Geostatistics, on the other hand, offers interpretable models of spatial (and spatiotemporal) dependence. This special issue on Geostatistics and Machine Learning aims to investigate applications of machine learning methods as well as hybrid approaches combining machine learning and geostatistics which advance our understanding and predictive ability of spatial processes.

Road performance and microscopic action mechanism of low liquid limit silt solidified by AT curing agent - Jin Chang; Jian-Qing Jiang; Ming Lei; Shi-Lin Luo; Guang-Feng He; Jia-Yi Lin (Arabian Journal of Geosciences, 2022)

Exosome-Derived lncRNA NEAT1 Exacerbates Sepsis-Associated Encephalopathy by Promoting Ferroptosis Through Regulating miR-9-5p/TFRC and GOT1 Axis - Xue-biao Wei; Wen-qiang Jiang; Ju-hao Zeng; Lin-qiang Huang; Hong-guang Ding; Yuan-wen Jing; Yong-li Han; Yi-chen Li; Sheng-long Chen (Molecular Neurobiology, 2022)
Sepsis can cause sepsis-associated encephalopathy (SAE), but whether SAE was induced or exacerbated by ferroptosis remains unknown. In this study, the rat sepsis model was constructed using the cecal ligation and puncture method. The blood–brain barrier (BBB) permeability was measured by Evans blue dye (EBD) in vivo. The levels of ROS, Fe ion, MDA, GSH, and GPX4 were assessed by enzyme-linked immunosorbent assay (ELISA). The exosomes isolated from serum were cultured with bEnd.3 cells for the in vitro analysis. Moreover, bEnd.3 cells cultured with 100 μM FeCl3 (iron-rich) were to simulate ferroptosis stress. The cell viability was evaluated by Cell Counting Kit-8 (CCK-8) assay. A dual-luciferase reporter gene assay was performed to confirm the relationship between miR-9-5p with NEAT1, TFRC , and GOT1 . In vivo, it is found that BBB permeability was damaged in model rats. Level of ROS, Fe ion, and MDA was increased, and level of GSH and GPX4 was decreased, which means ferroptosis was induced by sepsis. Exosome-packaged NEAT1 in serum was significantly upregulated in model rats. In vitro, it is found that NEAT1 functions as a ceRNA for miR-9-5p to facilitate TFRC and GOT1 expression. Overexpression of NEAT1 enhanced ferroptosis stress in bEnd.3 cells. Increased miR-9-5p alleviated sepsis-induced ferroptosis by suppressing the expression of TFRC and GOT1 both in vivo and in vitro. In conclusion, these findings suggest that sepsis induced high expression of serous exosome-derived NEAT1, and it might exacerbate SAE by promoting ferroptosis through regulating miR-9-5p/ TFRC and GOT1 axis.

Ethylene insensitive mutation alleviates cadmium-induced photosynthesis impairment in Arabidopsis plants - Qi-Yu Zhao; Chun-Xiu Gu; Yu Wang; Guang-Zhe Li; Lin Hao (Acta Physiologiae Plantarum, 2022)

Mitogenomes provide new insights into the evolutionary history of Prodiamesinae (Diptera: Chironomidae) - Xiao‐Long Lin; Yan‐Min Zhao; Li‐Ping Yan; Wen‐Bin Liu; Wen‐Jun Bu; Xin‐Hua Wang; Chen‐Guang Zheng (Zoologica Scripta, 2022)
Evolutionary analysis of Prodiamesinae has long been impeded by lack of information, and its phylogenetic relationship with Orthocladiinae remains questionable. Here, ten complete mitochondrial genomes (mitogenomes) of Orthocladiinae sensu lato were newly sequenced, including three Prodiamesinae species and seven Orthocladiinae species. Coupled with published mitogenomes, a total of 12 mitogenomes of Orthocladiinae sensu lato were selected for a comparative mitogenomic analysis and phylogenetic reconstruction. Mitogenomes of Orthocladiinae sensu lato are conserved in structure, and all genes arrange the same gene order as the ancestral insect mitogenome. Nucleotide composition is highly biased, and the control region displayed the highest A + T content. All protein‐coding genes are under purifying selection, and the ATP8 evolves at the fastest rate. In addition, the mitogenomes of Orthocladiinae sensu lato are highly conserved, and they are practically useful for phylogenetic inference, suggesting a re‐classification of Orthocladiinae by sinking Prodiamesinae as a subgroup of Orthocladiinae.

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

The Regulatory Relationships Between the Gonad-Inhibiting Hormone and Insulin-Like Androgenic Gland Hormone-Binding Protein Genes in the Eyestalk-Androgenic Gland-Testis Axis of Macrobrachium rosenbergii - Meizhen Tang; Zhijie Lu; Sarath V Babu; Guang Yang; Yanan Li; Zizheng Xu; Gan Pan; Zhendong Qin; Li Lin (Frontiers in Marine Science, 2021)
Gonad-inhibiting hormone (GIH) belongs to a family of neuropeptides that are released from the eyestalks of male crustaceans and plays key roles in gonadal maturity, reproduction, and molting. However, the detailed mechanisms underlying the effects of GIH on sexual regulation have yet to be elucidated. In the present study, we aimed to demonstrate how GIH mediate the activity of the androgenic gland (AG) to affect sexual regulation. To do this, we cloned and characterized a GIH sequence from Macrobrachium rosenbergii ( Mr GIH). The open reading frame (ORF) of Mr GIH was 360 bp and codes for a polypeptide of 119 amino acids and a putative protein of 13.56 KDa. Tissue analysis showed that Mr GIH is widely expressed in a range of tissues but particularly, the eyestalk, intestine, and nerve cord. Following the ds RNA silencing of Mr GIH for 24 h, the expression levels of Mr GIH were down-regulated in both the eyestalk and AG when compared with the negative control, but significantly increased the expression of Macrobrachium rosenbergii insulin-like androgenic gland hormone-binding protein ( Mr IAGBP) in AG, thus suggesting that Mr GIH is an inhibitory factor for Mr IAGBP. In addition, we found that eyestalk removal on certain days led to increased expression levels of Mr IAGBP expression. The expression levels of Mr IAGBP peaked at 2 d in the AG after unilateral and bilateral eyestalk ablation, exhibiting a 7.27- and 6.03-fold increase, respectively. Afterward, the expression of GIH protein levels were down-regulated and IAGBP protein levels were up-regulated after GIH silencing using immunohistochemistry method, combined with the increase of IAGBP protein levels after eyestalk ablation, confirming that Mr GIH is an inhibitory factor that can moderately regulate AG development and IAGBP expression. Collectively, our findings enriched the mechanisms that control the sexual regulation pathway of male M. rosenbergii , and provided significant information for further explorations of the mechanism underlying sex regulation in other decapod crustaceans.

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Shared and specific patterns of structural and functional thalamo-frontal disturbances in manic and euthymic pediatric bipolar disorder - Yi-Bing Guo; Wei-Jia Gao; Zhi-Liang Long; Wei-Fang Cao; Dong Cui; Yong-Xin Guo; Qing Jiao; Jian-Feng Qiu; Lin-Yan Su; Guang-Ming Lu (Brain Imaging and Behavior, 2021)
Bipolar disorder (BD) is clinically defined by alternating depressive and manic episodes with a separated period of euthymia. Thalamo-frontal loop plays vital role in psychotic symptoms, altered motor control and executive difficulties in BD. It remains unclear that structural and functional alterations of thalamo-frontal loop among the different mood states in BD, especially in pediatric BD(PBD). Twenty manic PBD (mPBD), 20 euthymic PBD (ePBD) and 19 healthy controls (HCs) were included in the study. By analyzing the T1 images and fMRI signals, thalamus volume and frontal grey matter cortical thickness were tested, and functional connectivity (FC) between bilateral thalamus and frontal cortex was calculated. Relationship between clinical indices and thalamo-frontal FC was also evaluated in mPBD and ePBD adolescents. Compared to HCs, the cortical thickness of left middle frontal gyrus (MFG), bilateral superior frontal gyrus (SFG) was significantly decreased in both mPBD and ePBD patients, and volume of left thalamus and cortical thickness of right MFG significantly decreased in mPBD patients. Compared to that of the HCs and ePBD subjects, thalamo-frontal hyperconnectivity with MFG was found in mPBD, and compared with that of HCs, thalamo-frontal hypoconnectivity with precentral gyrus/SFG was found in ePBD. In ePBD patients, episode times positively correlated with FC values between thalamus and precentral gyrus. The findings of the present study demonstrate detailed knowledge regarding shared and specific structural and functional disruption in thalamo-frontal loop in mPBD and ePBD subjects. Thalamo-frontal abnormalities reported in adult BD subjects were also observed in adolescent BD patients, and thalamo-frontal dysfunction may be a crucial treatment target in BD.

Correction to: A failure case study of tunnel water inrush source identified by statistical analysis model - Li-Gang Yuan; Xiao-Li Li; Xin Li; Yi-Lin Yu; Li-Guang Chen; Xian-Pan Xu; Xiang Wang (Arabian Journal of Geosciences, 2021)

Impacts of Marine Heatwaves on Algal Structure and Carbon Sequestration in Conjunction With Ocean Warming and Acidification - Guang Gao; Xin Zhao; Meijia Jiang; Lin Gao (Frontiers in Marine Science, 2021)
As the ocean warms, the frequency, duration, intensity, and range of marine heatwaves (MHWs) increase. MHWs are becoming a severe challenge for marine ecosystems. However, our understanding in regard to their impacts on algal structure and carbon sequestration is still deficient or fragmentary, particularly when combined with ocean warming and acidification. In this paper, we reviewed the impacts of MHWs individually and combined with ocean warming and acidification on regime shift in algal community and carbon sequestration of both macroalgae and microalgae. Solid evidence shows that MHWs cause the decline of large canopy macroalgae and increase of turf-forming macroalgae in abundance, leading to the regime shift from kelp forests to seaweed turfs. Furthermore, increased grazing pressure on kelps due to tropicalization facilitates the expansion of turfs that prevent the recovery of kelps through plundering light and space. Meanwhile, MHWs could trigger microalgal blooms and the intensity of algal blooms is regulated by the severity of MHWs and nutrient availability. MHWs could lead to the decrease of carbon burial and sequestration by canopy-forming macroalgae due to depressed growth and increased mortality. The effects of MHWs on the productivity of microalgae are latitude-dependent: negative effects at low and mid-latitudes whilst positive effects at high latitudes. Ocean warming and acidification may accelerate the shift from kelps to turfs and thus decrease the carbon sequestration by canopy-forming macroalgae further. We propose that MHWs combined with ocean warming and acidification would reduce the biodiversity and facilitate the thriving of morphologically simple, ephemeral and opportunistic turfs and diatoms in coastal oceans, and phytoplankton with smaller size in open oceans. This structure shift would not be in favor of long-term carbon sequestration. Future studies could be conducted to test this hypothesis and investigate the impacts of MHWs on carbon sequestration under future ocean conditions.

Rapid transition from MORB-type to SSZ-type oceanic crust generation following subduction initiation: insights from the mafic dikes and metamorphic soles in the Pozantı-Karsantı ophiolite, SE Turkey - Guang-Yao Xin; Yang Chu; Ben-Xun Su; Wei Lin; Ibrahim Uysal; Zhen-Tian Feng (Contributions to Mineralogy and Petrology, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Porcine circovirus type 2 (PCV2) infection in Hebei Province from 2016 to 2019: a retrospective study - Lei Han; Guang-fu Yuan; Shao-jie Chen; Fei Dai; Lin-shan Hou; Jing-hui Fan; Yu-zhu Zuo (Archives of Virology, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Roles of bulk and rhizosphere denitrifying bacteria in denitrification from paddy soils under straw return condition - Ning Wang; Ya-Hui Zhao; Jian-Guang Yu; Li-Hong Xue; Hong-Bo Li; Lin-Zhang Yang (Journal of Soils and Sediments, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

The response to flooding of two overwintering rice stem borers likely accounts for their changing impacts - Guang-Hua Luo; Zhi-Xin Luo; Zhi-Ling Zhang; Yang Sun; Ming-Hong Lu; Zhao-Lin Shu; Zi-Hua Tian; Ary A. Hoffmann; Ji-Chao Fang (Journal of Pest Science, 2021)

Prestack seismic stochastic inversion based on statistical characteristic parameters - Wang Bao-Li; Lin Ying; Zhang Guang-Zhi; Yin Xing-Yao; Zhao Chen (Applied Geophysics, 2021)

A chromosome-level genome assembly of the wild rice Oryza rufipogon facilitates tracing the origins of Asian cultivated rice - Xianrong Xie; Huilong Du; Huiwu Tang; Jianian Tang; Xiyu Tan; Weizhi Liu; Tie Li; Zhansheng Lin; Chengzhi Liang; Yao-Guang Liu (Science China Life Sciences, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Quantitative Determination of Glymphatic Flow Using Spectrophotofluorometry - Yu Zhang; Jian Song; Xu-Zhong He; Jian Xiong; Rong Xue; Jia-Hao Ge; Shi-Yu Lu; Die Hu; Guo-Xing Zhang; Guang-Yin Xu; Lin-Hui Wang (Neuroscience Bulletin, 2020)

A review of the Chinese monotypic genus Melliodendron (Styracaceae), with a new synonym of M. xylocarpum - Xue-Hui Wu; Rui Zhang; Timothy M. A. Utteridge; Yu-Lin Liu; Guang-Yao Yang; Ming Tang (Kew Bulletin, 2020)

EEG-based emotion recognition using 4D convolutional recurrent neural network - Fangyao Shen; Guojun Dai; Guang Lin; Jianhai Zhang; Wanzeng Kong; Hong Zeng (Cognitive Neurodynamics, 2020)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

MAPK pathway‐related tyrosine phosphatases regulate development, secondary metabolism and pathogenicity in fungus Aspergillus flavus - Guang Yang; Xiaohong Cao; Genli Ma; Ling Qin; Yuanzhen Wu; Jian Lin; Peng Ye; Jun Yuan; Shihua Wang (Environmental Microbiology, 2020)
Summary Mitogen‐activated protein kinase (MAPK) cascades are highly conserved in eukaryotic cells and are known to play crucial roles in the regulation of various cellular processes. However, compared with kinase‐mediated phosphorylation, dephosphorylation catalysed by phosphatases has not been well characterized in filamentous fungi. In this study, we identified five MAPK pathway‐related phosphatases (Msg5, Yvh1, Ptp1, Ptp2 and Oca2) and characterized their functions in Aspergillus flavus , which produces aflatoxin B 1 (AFB 1 ), one of the most toxic and carcinogenic secondary metabolites. These five phosphatases were identified as negative regulators of MAPK (Slt2, Fus3 and Hog1) pathways. Deletion of Msg5 and Yvh1 resulted in significant defects in conidiation, sclerotia formation, aflatoxin production and crop infection. Additionally, double knockout mutants (Δ Msg5/ Δ Ptp1 , Δ Msg5/ Δ Ptp2 and Δ Msg5/ Δ Oca2 ) displayed similar defects to those observed in the Δ Msg5 single mutant, indicating that Msg5 plays a major role in the regulation of development and pathogenicity in A . flavus . Importantly, we found that the active site at C439 is essential for the function of the Msg5 phosphatase. Furthermore, the MAP kinase Fus3 was found to be involved in the regulation of development, aflatoxin biosynthesis and pathogenicity, and its conserved phosphorylation residues (Thr and Tyr) were critical for the full range of its functions in A . flavus . Overall, our results reveal that MAPK related tyrosine phosphatases play important roles in the regulation of development, secondary metabolism and pathogenicity in A . flavus , and could be developed as potential targets for preventing damage caused by this fungal pathogen.

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Effect of recombinant human granulocyte colony-stimulating factor on lymphocyte subsets in patients with COVID-19 - Guang-Bin Chen; Jian-Tao Lin; Zheng Zhang; Lei Liu (Infectious Diseases, 2020)

Two new compounds from the heartwood of Dalbergia melanoxylon - Shuai Lin; Rong-Hua Liu; Guang-Qiang Ma; Dan-Yi Mei; Feng Shao; Lan-Ying Chen (Natural Product Research, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Modification-bioremediation of copper, lead, and cadmium-contaminated soil by combined ryegrass (Lolium multiflorum Lam.) and Pseudomonas aeruginosa treatment - Guang-yu Shi; Ying-jia Yan; Zhi-qiang Yu; Lu Zhang; Yuan-yuan Cheng; Wei-lin Shi (Environmental Science and Pollution Research, 2020)

Three new phenylacetamide glycosides from Dracocephalum tanguticum Maxim and their anti-hyperglycemic activity - En-Guang Ma; Hai-Yan Wu; Li-Jiao Hu; Min Wei; Lin-Yun Mou; Gan-Peng Li (Natural Product Research, 2020)

Efficacy of fluopyram as a candidate trunk-injection agent against Bursaphelenchus xylophilus - Guangying Liu; Xu Lin; Shuangyu Xu; Guang Liu; Zhenyu Liu; Feng Liu; Wei Mu (European Journal of Plant Pathology, 2020)

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

A chronosequence study of purple paddy soils with respect to improving ammonium and potassium fertilization management - Guang-Zhong Han; Lai-Ming Huang; Gan-Lin Zhang; Fan Yang (Journal of Soils and Sediments, 2020)

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Heat stress induces apoptosis through disruption of dynamic mitochondrial networks in dairy cow mammary epithelial cells - Kun-Lin Chen; Hui-Li Wang; Lin-Zheng Jiang; Yong Qian; Cai-Xia Yang; Wei-Wei Chang; Ji-Feng Zhong; Guang-Dong Xing (In Vitro Cellular & Developmental Biology - Animal, 2020)

The roles of moisture transports in intraseasonal precipitation during the preflood season over South China - Qu‐cheng Chu; Qi‐guang Wang; Guo‐lin Feng (International Journal of Climatology, 2020)
The roles of moisture sources and transport in intraseasonal precipitation variabilities during the preflood season over South China are complex and different. In this paper, ERA‐Interim reanalysis data that were collected four times daily from 1979 to 2017 are used to analyse the variation and influence of moisture transport in intraseasonal precipitation during the preflood season over South China. Using the Hybrid Single‐Particle Lagrangian Integrated Trajectory model, fixed atmospheric moisture sources are defined: land area source (LD source), Indian Ocean source (IO source), Pacific Ocean source (PO source), South China Sea source (SCS source), and South China source (SC source). Sea source moisture transport accounts for more than 75% of the total precipitation during the preflood season, which is the most important moisture source in South China. For April, southeasterly moisture transport, which includes PO source and SCS source moisture transports, is the major moisture transport over South China. Then, the IO source and SCS source precipitation increased significantly during May. During June, the IO source precipitation accounted for 43.75% of the total precipitation, thus dominating precipitation over South China. In addition, there is a significant difference in the interdecadal variation in the preflood season precipitation before and after the Indian summer monsoon onset. Before the Indian summer monsoon onset, the land‐sea thermal contrast decreased, which led to a significant interdecadal reduction in the IO source, PO source, and SCS source moisture transports. After the Indian summer monsoon onset, the increase in IO source moisture transport is the primary cause of the interdecadal increase in precipitation over South China.

Water quality monitoring at a virtual watershed monitoring station using a modified deep extreme learning machine - Jian Jin; Peng Jiang; Lei Li; Huan Xu; Guang Lin (Hydrological Sciences Journal, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

Mbp1, a component of the MluI cell cycle box‐binding complex, contributes to morphological transition and virulence in the filamentous entomopathogenic fungus Beauveria bassiana - Jin‐Li Ding; Hai‐Yan Lin; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2020)
Summary The Mbp1 protein functions as a DNA‐binding protein in the MluI cell cycle box‐binding complex and plays significant roles in yeast development. In this study, an ortholog of yeast Mbp1, BbMbp1, was characterized in a filamentous insect mycopathogen, Beauveria bassiana . BbMbp1 plays an important role in morphological changes under aerial and liquid environments. On the aerial surface, BbMbp1 was indispensable for the biogenesis of conidiophores and conidiation. Under submerged conditions, the ∆ BbMbp1 mutant displayed abnormal spore‐producing structures, with a dramatic decrease in blastospore yield (~95%). The virulence of the ∆ BbMbp1 mutant was notably weakened, which might be due to the defect in in vivo blastospore formation in the insect. Moreover, disruption of BbMbp1 resulted in a substantial reduction in hyphal growth on cadavers. Comparative transcriptomics revealed that BbMbp1 mediated different transcriptomes during the formation processes of conidia and blastospores. Yeast one‐hybrid assays demonstrated that BbMbp1 was required for transcriptional control of a cell wall protein gene, BbCwp , and an integral membrane protein gene, BbImp that played significant roles in conidiation and blastospore formation respectively. Our results demonstrate that BbMbp1 contributes to the morphological transitions in the pathogenic and saprophytic growth of B . bassiana via different genetic pathways.

Metabolomic profiling on rat brain of prenatal malnutrition: implicated for oxidative stress and schizophrenia - Fei Xu; Xin Li; Weibo Niu; Gaini Ma; Qianqian Sun; Yan Bi; Zhenming Guo; Decheng Ren; Jiaxin Hu; Fan Yuan; Ruixue Yuan; Lei Shi; et al. (Metabolic Brain Disease, 2019)

Whitlockite Promotes Bone Healing in Rabbit Ilium Defect Model - Yuan-Zhe Jin; Guang-Bin Zheng; Hae Lin Jang; Kyung Mee Lee; Jae Hyup Lee (Journal of Medical and Biological Engineering, 2019)

Roles of moisture sources and transport in precipitation variabilities during boreal summer over East China - Qu-cheng Chu; Rong Zhi; Qi-guang Wang; Guo-lin Feng (Climate Dynamics, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Landslide detection in La Paz City (Bolivia) based on time series analysis of InSAR data - Chao Huang Lin; Dawei Liu; Guang Liu (International Journal of Remote Sensing, 2019)

Seroprevalence of porcine bocavirus in pigs in north-central China using a recombinant-NP1-protein-based indirect ELISA - Qian-Kai Shi; Jian-Lou Zhang; Wen-Yuan Gu; Lin-Shan Hou; Guang-Fu Yuan; Shao-Jie Chen; Jing-Hui Fan; Yu-Zhu Zuo (Archives of Virology, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

Water quality prediction based on recurrent neural network and improved evidence theory: a case study of Qiantang River, China - Lei Li; Peng Jiang; Huan Xu; Guang Lin; Dong Guo; Hui Wu (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Dynamic changes in lakes in the Hoh Xil region before and after the 2011 outburst of Zonag Lake - Wen-hui Liu; Chang-wei Xie; Lin Zhao; Tong-hua Wu; Wu Wang; Yu-xin Zhang; Gui-qian Yang; Xiao-fan Zhu; Guang-yang Yue (Journal of Mountain Science, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

Relationships between body weight and other morphological traits in young sea cucumbers Apostichopus japonicas - Yaoyao Zhan; Weijie Zhang; Chen Ge; Kai Lin; Guang Li; Jian Song; Yaqing Chang (Journal of Oceanology and Limnology, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Different Impacts from Various El Niño Events on Wyrtki Jets in Boreal Autumn Season - Yue Wu; Lin Liu; Xinyou Zhang; Yongliang Duan; Guang Yang; Yang Yang; Zahid; Paul Oloo; Philip Sagero (Pure and Applied Geophysics, 2018)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Risk factors and drug resistance in early-onset neonatal group B streptococcal disease - Ying-wei Wang; Yao-qiang Du; Xiao-lin Miao; Guang-yong Ye; Yi-yun Wang; Ai-bo Xu; Yun-zhong Jing; Yu Tong; Kai Xu; Mei-qin Zheng; Dong Chen; Zhen Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

Survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen Bay, China - Bingyao Chen; Huili Gao; Thomas A. Jefferson; Yi Lu; Lin Wang; Shanshan Li; Hui Wang; Xinrong Xu; Guang Yang (Marine Mammal Science, 2018)
The survival rate and population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in Xiamen, China, were estimated from vessel‐based surveys during 2007–2010. Over the course of 202 d (881.1 observation hours), 76 groups were observed, and 52 dolphins were successfully identified. The Cormack‐Jolly‐Seber model estimated a constant apparent survival of 0.948 (95% CI: 0.922–0.966). Based on the open/POPAN model, the population size was estimated at 70 individuals (95% CI: 63–88). To explore the effect of uneven yearly survey effort, we pooled the data with seven sampling occasions with similar effort. This data set generated similar results of a constant survival of 0.957 (95% CI: 0.918–0.978) and population size of 72 (95% CI: 65–88). The small population size of the Xiamen humpback dolphins satisfies the Critically Endangered criterion of IUCN (D), and emphasizes urgency of the need for protection of the population. Improved monitoring efforts should be focused on enhancing our understanding of current status and evaluating impacts of all anthropogenic activities. A conservation plan for the population should also be drawn up.

The genome sequence of ‘Kurodagosun’, a major carrot variety in Japan and China, reveals insights into biological research and carrot breeding - Feng Wang; Guang-Long Wang; Xi-Lin Hou; Meng-Yao Li; Zhi-Sheng Xu; Ai-Sheng Xiong (Molecular Genetics and Genomics, 2018)

Methyl jasmonate and salicylic acid elicitation increase content and yield of chlorogenic acid and its derivatives in Gardenia jasminoides cell suspension cultures - Ze-Bo Liu; Ji-Guang Chen; Zhong-Ping Yin; Xin-Chen Shangguan; Da-Yong Peng; Tao Lu; Ping Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Low-level concentrations of aminoglycoside antibiotics induce the aggregation of cyanobacteria - Lin-Rui Tan; Peng-Fei Xia; Raymond J. Zeng; Qian Li; Xue-Fei Sun; Shu-Guang Wang (Environmental Science and Pollution Research, 2018)

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Histone 3 lysine 36 to methionine mutations stably interact with and sequester SDG8 in Arabidopsis thaliana - Guang Lin; Ying Zhou; Min Li; Yuda Fang (Science China Life Sciences, 2018)

Ca2+-CaMKKβ pathway is required for adiponectin-induced secretion in rat submandibular gland - Chong Ding; Zhi-Hao Du; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2018)

The relationship between genetic polymorphisms in apolipoprotein E (ApoE) gene and osteonecrosis of the femoral head induced by steroid in Chinese Han population - Lin Yuan; Wei Li; Xianquan Wang; Guang Yang; Haiyang Yu; Shui Sun (Genes & Genomics, 2018)

Feature analysis and primary causes of pre-flood season “cumulative effect” of torrential rain over South China - Qu-cheng Chu; Qi-guang Wang; Shao-bo Qiao; Guo-lin Feng (Theoretical and Applied Climatology, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Productive functional evolution of rural settlements: analysis of livelihood strategy and land use transition in eastern China - Bai-lin Zhang; Guang-hui Jiang; Wei-min Cai; Pi-ling Sun; Feng-rong Zhang (Journal of Mountain Science, 2017)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

C5a/C5aR Pathway Plays a Vital Role in Brain Inflammatory Injury via Initiating Fgl-2 in Intracerebral Hemorrhage - Bangqing Yuan; Fenlan Fu; Shaokuan Huang; Chuangan Lin; Guang Yang; Kunlong Ma; Hui Shi; Zhao Yang (Molecular Neurobiology, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

N-Myc Downstream-Regulated Gene 2 (Ndrg2) Is Involved in Ischemia–Hypoxia-Induced Astrocyte Apoptosis: a Novel Target for Stroke Therapy - Yu-Long Ma; Li-xia Zhang; Guang-lin Liu; Yanhong Fan; Ye Peng; Wu-Gang Hou (Molecular Neurobiology, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Follistatin-like protein 1 suppressed pro-inflammatory cytokines expression during neuroinflammation induced by lipopolysaccharide - Kai-Yuan Cheng; Yi Liu; Ying-Guang Han; Jing-Kun Li; Jia-Lin Jia; Bin Chen; Zhi-Xiao Yao; Lin Nie; Lei Cheng (Journal of Molecular Histology, 2017)

Chemical composition of Illicium verum fruit extract and its bioactivity against the peach–potato aphid, Myzus persicae (Sulzer) - Shi-Guang Li; Ben-Guo Zhou; Mao-Ye Li; Su Liu; Ri-Mao Hua; Hua-Feng Lin (Arthropod-Plant Interactions, 2017)

Rock burst assessment in multi-seam mining: a case study - Wei Shen; Lin-ming Dou; Hu He; Guang-an Zhu (Arabian Journal of Geosciences, 2017)

Congenic mapping identifies a novel Idd9 subregion regulating type 1 diabetes in NOD mice - Bixuan Lin; Ashley E. Ciecko; Erin MacKinney; David V. Serreze; Yi-Guang Chen (Immunogenetics, 2017)

Variation in carbohydrates and screening of related differential proteins during the seed germination of Magnolia sieboldii K. Koch - Mei Mei; Xiu-jun Lu; Xiao-lin Zhang; Guang-lin Liu; Xiao-mei Sun (Trees, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

First discovery of a Palaeoproterozoic A-type granite in southern Wuyishan terrane, Cathaysia Block: evidence from geochronology, geochemistry, and Nd–Hf–O isotopes - Zhi-Hong Chen; Ling Zhao; Dan-Dan Chen; Xi-Lin Zhao; Guang-Fu Xing (International Geology Review, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Limit analysis method for active earth pressure on laggings between stabilizing piles - Ming-min Wang; Shu-guang Wu; Gui-lin Wang (Journal of Mountain Science, 2017)

Features and origin time of Mesozoic strike-slip structures in the Yilan-Yitong Fault Zone - ChengChuan Gu; Guang Zhu; MingJian Zhai; ShaoZe Lin; LiHong Song; Bei Liu (Science China Earth Sciences, 2016)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Generating Random Earthquake Events for Probabilistic Tsunami Hazard Assessment - Randall J. LeVeque; Knut Waagan; Frank I. González; Donsub Rim; Guang Lin (Pure and Applied Geophysics, 2016)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Distribution of soil carbon in different grassland types of the Qinghai-Tibetan Plateau - Shu-li Liu; Yan-gong Du; Fa-wei Zhang; Li Lin; Yi-kang Li; Xiao-wei Guo; Qian Li; Guang-min Cao (Journal of Mountain Science, 2016)

The adipokine Chemerin induces lipolysis and adipogenesis in bovine intramuscular adipocytes - Yuan-Yuan Fu; Kun-Lin Chen; Hui-Xia Li; Guang-Hong Zhou (Molecular and Cellular Biochemistry, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Palaeoproterozoic A-type magmatism in northern Wuyishan terrane, Southeast China: petrogenesis and tectonic implications - Zhi-Hong Chen; Guang-Fu Xing; Xi-Lin Zhao (International Geology Review, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Blockade of CD127 Exerts a Dichotomous Clinical Effect in Marmoset Experimental Autoimmune Encephalomyelitis - Jordon Dunham; Li-Fen Lee; Nikki van Driel; Jon D. Laman; Irene Ni; Wenwu Zhai; Guang-Huan Tu; John C. Lin; Jan Bauer; Bert A. ‘t Hart; Yolanda S. Kap (Journal of Neuroimmune Pharmacology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Carbon stock of larch plantations and its comparison with an old-growth forest in northeast China - Guang Qi; Hua Chen; Li Zhou; Xinchuang Wang; Wangming Zhou; Lin Qi; Yuhua Yang; Fengling Yang; Qingli Wang; Limin Dai (Chinese Geographical Science, 2016)

Notch2 signaling contributes to cell growth, invasion, and migration in salivary adenoid cystic carcinoma - Jing Qu; Min Song; Jian Xie; Xiao-Yu Huang; Xiao-Meng Hu; Rui-Huan Gan; Yong Zhao; Li-Song Lin; Jiang Chen; Xu Lin; Da-Li Zheng; You-Guang Lu (Molecular and Cellular Biochemistry, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Perceived reputation of others modulates empathic neural responses - Li Zheng; Qianfeng Wang; Xuemei Cheng; Lin Li; Guang Yang; Lining Sun; Xiaoli Ling; Xiuyan Guo (Experimental Brain Research, 2016)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Pseudonocardia nematodicida sp. nov., isolated from mangrove sediment in Hainan, China - Min Liu; Shan-shan Xing; Wei-dao Yuan; Hua Wei; Qian-guang Sun; Xiang-zhi Lin; Hui-qin Huang; Shi-xiang Bao (Antonie van Leeuwenhoek, 2015)

Effects of MAL61 and MAL62 overexpression on maltose fermentation of baker’s yeast in lean dough - Cui-Ying Zhang; Xue Lin; Hai-Yan Song; Dong-Guang Xiao (World Journal of Microbiology and Biotechnology, 2015)

Effects of Polypropylene Carbonate/Poly(d,l-lactic) Acid/Tricalcium Phosphate Elastic Composites on Improving Osteoblast Maturation - Hsu-Wei Fang; Wei-Yu Kao; Pei-I Lin; Guang-Wei Chang; Ya-Jung Hung; Ruei-Ming Chen (Annals of Biomedical Engineering, 2015)

Soil organic matter fractions under different vegetation types in permafrost regions along the Qinghai-Tibet Highway, north of Kunlun Mountains, China - Wen Shang; Lin Zhao; Xiao-dong Wu; Yu-qiang Li; Guang-yang Yue; Yong-hua Zhao; Yong-ping Qiao (Journal of Mountain Science, 2015)

Endoplasmic Reticulum Stress: Relevance and Therapeutics in Central Nervous System Diseases - Hong-Yu Zhang; Zhou-guang Wang; Xiang-Hong Lu; Xiao-Xia Kong; Fen-Zan Wu; Li Lin; Xiaohua Tan; Li-Bing Ye; Jian Xiao (Molecular Neurobiology, 2015)

Nocardiopsis mangrovei sp. nov., isolated from mangrove sediment - Hui-qin Huang; Shan-shan Xing; Wei-dao Yuan; Ying Wang; Min Liu; Qian-guang Sun; Xiang-zhi Lin; Shi-xiang Bao (Antonie van Leeuwenhoek, 2015)

Investigation of the hazardous substance causing crayfish-induced rhabdomyolysis via a mouse model, a hemolysis assay, and a cytotoxicity assay - Xiao-Feng Chen; Jiang-Wei Lin; Tzu-Ming Pan; Min-Jie Cao; Chao-Lan Shi; Qiu-Feng Cai; Guang-Ming Liu (Fisheries Science, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Fast-growing and poorly shade-tolerant invasive species may exhibit higher physiological but not morphological plasticity compared with non-invasive species - Yu-Ping Hou; Shao-Lin Peng; Zhen-Guang Lin; Qiao-Qiao Huang; Guang-Yan Ni; Na Zhao (Biological Invasions, 2015)

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid - Hung-Yu Shu; Ling-Chun Lin; Tze-Kang Lin; Hao-Ping Chen; Hsueh-Hui Yang; Kou-Cheng Peng; Guang-Huey Lin (Antonie van Leeuwenhoek, 2015)

Induction of plant virus defense response by brassinosteroids and brassinosteroid signaling in Arabidopsis thaliana - Da-Wei Zhang; Xing-Guang Deng; Fa-Qiong Fu; Hong-Hui Lin (Planta, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Pedogenetic evolution of clay minerals and agricultural implications in three paddy soil chronosequences of south China derived from different parent materials - Guang-Zhong Han; Gan-Lin Zhang; De-Cheng Li; Jin-Ling Yang (Journal of Soils and Sediments, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Seroprevalence and molecular detection of Mycoplasma ovipneumoniae in goats in tropical China - Guang Rong; Jun-Ming Zhao; Guan-Yu Hou; Han-Lin Zhou (Tropical Animal Health and Production, 2014)

USP11 regulates p53 stability by deubiquitinating p53 - Jia-ying Ke; Cong-jie Dai; Wen-lin Wu; Jin-hua Gao; Ai-juan Xia; Guang-ping Liu; Kao-sheng Lv; Chun-lin Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Protolith ages and deformation mechanism of metamorphic rocks in the Zhangbaling uplift segment of the Tan-Lu Fault Zone - Tian Zhao; Guang Zhu; ShaoZe Lin; LeJia Yan; QinQin Jiang (Science China Earth Sciences, 2014)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

In vitro cytotoxicity, cell cycle arrest, and antioxidation studies of ruthenium(II) complex [Ru(dmb)2(AHPIP)](ClO4)2 - De-Gang Xing; Yan Zhang; Gan-Jian Lin; Yang-Yin Xie; Shu-Yong Deng; Hong-Liang Huang; Guang-Bin Jiang; Yun-Jun Liu (Medicinal Chemistry Research, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Major alterations in transcript profiles between C3–C4 and C4 photosynthesis of an amphibious species Eleocharis baldwinii - Taiyu Chen; Xin-Guang Zhu; Yongjun Lin (Plant Molecular Biology, 2014)

Microseismic and acoustic emission effect on gas outburst hazard triggered by shock wave: a case study - Cai-Ping Lu; Lin-Ming Dou; Nong Zhang; Jun-Hua Xue; Guang-Jian Liu (Natural Hazards, 2014)

A more sensitive and rapid multiplex RT-PCR assay combining with magnetic nanobeads for simultaneous detection of viruses in sweet potato - Xing-Guang Deng; Feng Zhu; Ying-Juan Chen; Jian Liu; Tong Zhu; Jing-Yi Li; De-Hui Xi; Hong-Hui Lin (European Journal of Plant Pathology, 2014)

Establishment of Rat Model of Central Venous Catheter (CVC): Associated Infection and Evaluation of the Virulence of Bacterial Biofilms - Lian-Hua Ye; Yun-Chao Huang; Feng-Li Guo; Xin Liu; Guang-Qiang Zhao; Lin-Can Duan; Cong-Guo Jin (Cell Biochemistry and Biophysics, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

The protective effect of rosmarinic acid on hyperthermia-induced C2C12 muscle cells damage - Kun-Lin Chen; Hui-Xia Li; Xing-Lian Xu; Guang-Hong Zhou (Molecular Biology Reports, 2014)

The role of serine 190 in FOXO nuclear export and cell death induction in Drosophila melanogaster - Yoon Ki Hong; Dahye Lee; Soojin Hwang; Se Min Bang; Haemin Jeong; Seoyun Choi; Tan-Viet Phamd; Lin-Woo Kang; Young-Ha Lee; Kyoung Sang Cho; Guang-Ho Cha (Genes & Genomics, 2014)

Differential proteome analysis of mature and germinated seeds of Magnolia sieboldii K. Koch - Xiao-lin Zhang; Guang-lin Liu; Tian-lai Li; Ming-fang Qi; Mei Mei; Xiu-jun Lu (Trees, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

Neotectonic activity and formation mechanism of the Yishu Fault Zone - LeJia Yan; Guang Zhu; ShaoZe Lin; Tian Zhao (Science China Earth Sciences, 2014)

The Chilli Veinal Mottle Virus Regulates Expression of the Tobacco Mosaic Virus Resistance Gene N and Jasmonic Acid/Ethylene Signaling Is Essential for Systemic Resistance Against Chilli Veinal Mottle Virus in Tobacco - Feng Zhu; De-Hui Xi; Xing-Guang Deng; Xing-Ji Peng; He Tang; Ying-Juan Chen; Wei Jian; Hong Feng; Hong-Hui Lin (Plant Molecular Biology Reporter, 2014)

High-density lipoprotein induces cyclooxygenase-2 expression and prostaglandin I-2 release in endothelial cells through sphingosine kinase-2 - Sheng-Lin Xiong; Xing Liu; Guang-Hui Yi (Molecular and Cellular Biochemistry, 2014)

Functional Analysis of a Novel Chrysanthemum WRKY Transcription Factor Gene Involved in Salt Tolerance - Qing-Lin Liu; Ke-Dong Xu; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Plant Molecular Biology Reporter, 2014)

Effects of intercropping with Atractylodes lancea and application of bio-organic fertiliser on soil invertebrates, disease control and peanut productivity in continuous peanut cropping field in subtropical China - Xiao-gang Li; Xing-xiang Wang; Chuan-chao Dai; Tao-lin Zhang; Xing-guang Xie; Chang-feng Ding; Hong-wei Wang (Agroforestry Systems, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Cytotoxicity, apoptosis, cell cycle arrest, reactive oxygen species, mitochondrial membrane potential, and Western blotting analysis of ruthenium(II) complexes - Gan-Jian Lin; Guang-Bin Jiang; Yang-Yin Xie; Hong-Liang Huang; Zhen-Hua Liang; Yun-Jun Liu (JBIC Journal of Biological Inorganic Chemistry, 2013)

Verapamil Reverses Myocardial No-Reflow After Primary Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction - Qiang Fu; Wen Lu; Yi-jie Huang; Qiang Wu; Lin-guang Wang; Hai-bo Wang; Shu-zhong Jiang; Yan-jiong Wang (Cell Biochemistry and Biophysics, 2013)

Overexpression of a novel chrysanthemum Cys2/His2-type zinc finger protein gene DgZFP3 confers drought tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Ming Zhong; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Biotechnology Letters, 2013)

An Uncertainty Quantification Framework for Studying the Effect of Spatial Heterogeneity in Reservoir Permeability on CO2 Sequestration - Zhangshuan Hou; Dave W. Engel; Guang Lin; Yilin Fang; Zhufeng Fang (Mathematical Geosciences, 2013)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Flavonoids from Millettia nitida var. hirsutissima with their anticoagulative activities and inhibitory effects on NO production - Xiao-Lin Liao; Jian-Guang Luo; Ling-Yi Kong (Journal of Natural Medicines, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Pestalotiopsis yunnanensis sp. nov., an endophyte from Podocarpus macrophyllus (Podocarpaceae) based on morphology and ITS sequence data - Ji-Guang Wei; Cong-Kien Phan; Lin Wang; Tong Xu; Ji-Tong Luo; Xiang Sun; Liang-Dong Guo (Mycological Progress, 2013)

Organic acids on the growth, anatomical structure, biochemical parameters and heavy metal accumulation of Iris lactea var. chinensis seedling growing in Pb mine tailings - Yu-Lin Han; Su-Zhen Huang; Hai-Yan Yuan; Jiu-Zhou Zhao; Ji-Guang Gu (Ecotoxicology, 2013)

A new sesquiterpene glucoside from Nicotiana rustica L. - Rong Zhou; Dong-Liang Li; Guang-Lin Feng; Guo-You Li (Natural Product Research, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Combined action of antioxidant defense system and osmolytes in chilling shock-induced chilling tolerance in Jatropha curcas seedlings - Zhong-Guang Li; Ling-Xuan Yuan; Qiu-Lin Wang; Zhi-Liu Ding; Chun-Yan Dong (Acta Physiologiae Plantarum, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2013)

Iron Overload Inhibits Osteoblast Biological Activity Through Oxidative Stress - Yin-Feng He; Yong Ma; Chao Gao; Guo-yang Zhao; Lin-Lin Zhang; Guang-Fei Li; Yun-Zhi Pan; Kai Li; You-Jia Xu (Biological Trace Element Research, 2013)

Influence of CYP2C19 loss-of-function variants on the antiplatelet effects and cardiovascular events in clopidogrel-treated Chinese patients undergoing percutaneous coronary intervention - Jian-Jun Zou; Hong-Guang Xie; Shao-Liang Chen; Jie Tan; Ling Lin; Ying-Ying Zhao; Hai-Mei Xu; Song Lin; Juan Zhang; Guang-Ji Wang (European Journal of Clinical Pharmacology, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Paenibacillus beijingensis sp. nov., a novel nitrogen-fixing species isolated from jujube garden soil - Miao Gao; Lin-qi Xie; Ya-xiong Wang; Jian Chen; Jing Xu; Xiao-xia Zhang; Xin-hua Sui; Jun-lian Gao; Jian-guang Sun (Antonie van Leeuwenhoek, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Protoplast isolation and culture for somatic hybridisation of rapid cycling Brassica rapa with ‘Anand’ CMS and Brassica juncea - Yu-Ji Lian; Xiao-Mei Zhao; Guang-Zhe Lin; Hak-tae Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Morphological and photosynthetic variations in the process of spermatia formation from vegetative cells in Porphyra yezoensis Ueda (Bangiales, Rhodophyta) and their responses to desiccation - Rui-Ling Yang; Wei Zhou; Song-Dong Shen; Guang-Ce Wang; Lin-Wen He; Guang-Hua Pan (Planta, 2012)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Aircraft noise exposure affects rat behavior, plasma norepinephrine levels, and cell morphology of the temporal lobe - Guo-qing Di; Bing Zhou; Zheng-guang Li; Qi-li Lin (Journal of Zhejiang University-SCIENCE B, 2011)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

Overexpression of a novel chrysanthemum NAC transcription factor gene enhances salt tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Liang-Jun Zhao; Yuan-Zhi Pan; Bei-Bei Jiang; Hai-Qing Zhang; Guang-Li Liu (Biotechnology Letters, 2011)

Somatic embryogenesis and shoot organogenesis in the medicinal plant Pulsatilla koreana Nakai - Guang-Zhe Lin; Xiao-Mei Zhao; Soon-Kwan Hong; Yu-Ji Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Combined administration of D-galactose and aluminium induces Alzheimerlike lesions in brain - Fei Xiao; Xiao-Guang Li; Xiao-Yu Zhang; Jun-Dai Hou; Lian-Feng Lin; Qin Gao; Huan-Min Luo (Neuroscience Bulletin, 2011)

The influence of genetic polymorphisms and interacting drugs on initial response to warfarin in Chinese patients with heart valve replacement - Shi-Long Zhong; Yuan Liu; Xi-Yong Yu; Dan Xu; Hong-Hong Tan; Qiu-Xiong Lin; Min Yang; Hai-Yan Lao; Shu-Guang Lin (European Journal of Clinical Pharmacology, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Serum Trace Element Levels in Tuberculous Pleurisy - Guang-Qiang Wang; Mei-Ying Lin (Biological Trace Element Research, 2011)

Delineation of the translocation of colicin E7 across the inner membrane of Escherichia coli - Yuh-Ren Chen; Tsung-Yeh Yang; Guang-Sheng Lei; Lung-JR Lin; Kin-Fu Chak (Archives of Microbiology, 2011)

Production and genetic characterization of somatic hybrids between leaf mustard (Brassica juncea) and broccoli (Brassica oleracea) - Yu-Ji Lian; Guang-Zhe Lin; Xiao-Mei Zhao; Hak-Tae Lim (In Vitro Cellular & Developmental Biology - Plant, 2011)

Verapamil exerts biphasic modulation on phenobarbital transport across the blood–brain barrier: evidence from an in vivo and in vitro study - Dan Yao; Zhi-Hong Yang; Li Liu; Jia Li; Yun-Li Yu; Lu-Lu Zhang; Xian Pan; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Effect of polar-dissolved organic matter fractions on the mobility of prometryne in soil - Guang Chen; Chao Lin; Liang Chen; Hong Yang (Journal of Soils and Sediments, 2011)

Chemical-protein interactome and its application in off-target identification - Lun Yang; Ke-Jian Wang; Li-Shan Wang; Anil G. Jegga; Sheng-Ying Qin; Guang He; Jian Chen; Yue Xiao; Lin He (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Atypical Class 1 Integron Coexists with Class 1 and Class 2 Integrons in Multi-Drug Resistant Shigella flexneri Isolates from China - Jing Yuan Zhu; Guang Cai Duan; Hai Yan Yang; Qing Tang Fan; Yuan Lin Xi (Current Microbiology, 2011)

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China - Yu-Ping Hou; Shao-Lin Peng; Bao-Ming Chen; Guang-Yan Ni (Biological Invasions, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

A checklist of the cultivated plants of Yunnan (PR China) - Chun-Yan Li; Guang-Yong Zhang; Karl Hammer; Chun-Yan Yang; Chun-Lin Long (Genetic Resources and Crop Evolution, 2011)

Effect of blue light on indoor seedling culture of Saccharina japonica (Phaeophyta) - Wen-Jun Wang; Xiu-Tao Sun; Guang-Ce Wang; Pu Xu; Xiang-Yu Wang; Zhe-Long Lin; Fei-Jiu Wang (Journal of Applied Phycology, 2010)

Acroptilon repens, an Asian invader, has stronger competitive effects on species from America than species from its native range - Guang-Yan Ni; Urs Schaffner; Shao-Lin Peng; Ragan M. Callaway (Biological Invasions, 2010)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Identification of p27/KIP1 expression level as a candidate biomarker of response to rapalogs therapy in human cancer - Guang Chen; Na Yang; Xiang Wang; Si-Yuan Zheng; Yi Chen; Lin-Jiang Tong; Yi-Xue Li; Ling-Hua Meng; Jian Ding (Journal of Molecular Medicine, 2010)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Biodelignification of rice straw by Phanerochaete chrysosporium in the presence of dirhamnolipid - Yun-Shan Liang; Xing-Zhong Yuan; Guang-Ming Zeng; Chen-Lu Hu; Hua Zhong; Dan-Lian Huang; Lin Tang; Jia-Jia Zhao (Biodegradation, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

Lophodermium on needles of conifers from Yunnan Province, China - Jian-Tang Luo; Ying-Ren Lin; Guang-Kai Shi; Cheng-Lin Hou (Mycological Progress, 2010)

Changes of Sex Pheromone Communication Systems Associated with Tebufenozide and Abamectin Resistance in Diamondback Moth, Plutella xylostella (L.) - Zhen Xu; Guang-Chun Cao; Shuang-Lin Dong (Journal of Chemical Ecology, 2010)

Berberine suppresses intestinal disaccharidases with beneficial metabolic effects in diabetic states, evidences from in vivo and in vitro study - Li Liu; Yun-Li Yu; Jian-Song Yang; Yang Li; Yao-Wu Liu; Yan Liang; Xiao-Dong Liu; Lin Xie; Guang-Ji Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Platinum-group minerals and tellurides from the PGE-bearing Xinjie layered intrusion in the Emeishan Large Igneous Province, SW China - Wei-Guang Zhu; Hong Zhong; Rui-Zhong Hu; Bing-Guang Liu; De-Feng He; Xie-Yan Song; Hai-Lin Deng (Mineralogy and Petrology, 2010)

Nutrient conservation strategies of a mangrove species Rhizophora stylosa under nutrient limitation - Yi-Ming Lin; Xiao-Wei Liu; Hui Zhang; Hang-Qing Fan; Guang-Hui Lin (Plant and Soil, 2010)

The physiological response and sub-cellular localization of lead and cadmium in Iris pseudacorus L. - Yu-Qing Zhou; Su-Zhen Huang; Shi-Long Yu; Ji-Guang Gu; Jiu-Zhou Zhao; Yu-Lin Han; Jia-Jia Fu (Ecotoxicology, 2010)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Effects of the invasive plant Mikania micrantha H.B.K. on soil nitrogen availability through allelopathy in South China - Bao-Ming Chen; Shao-Lin Peng; Guang-Yan Ni (Biological Invasions, 2009)

Inhibition of NFkappaB by activated c-Jun NH2 terminal kinase 1 acts as a switch for C2C12 cell death under excessive stretch - Jiali Tan; Wei Kuang; Zuolin Jin; Fang Jin; Lin Xu; Qiujun Yu; Liang Kong; Guang Zeng; Xiao Yuan; Yinzhong Duan (Apoptosis, 2009)

Z f-and-H sys-based C m measurement under the whole-cell patch-clamp recording - Hao Zhang; Jie Luo; Jun Xiong; Xian-Guang Lin; Zheng-Xing Wu; Anlian Qu (Pflügers Archiv - European Journal of Physiology, 2009)

Gene mapping related to yellow green leaf in a mutant line in rice (Oryza sativa L.) - Peng Du; Ying-Hua Ling; Xian-Chun Sang; Fang-Ming Zhao; Rong Xie; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

Photosynthetic parameters of sexually different parts of Porphyra katadai var. hemiphylla (Bangiales, Rhodophyta) during dehydration and re-hydration - A-Peng Lin; Guang-Ce Wang; Fang Yang; Guang-Hua Pan (Planta, 2009)

Proteome alteration of U251 human astrocytoma cell after inhibiting retinoic acid synthesis - Ming Zhang; Chunling Wan; Baohu Ji; Zhao Zhang; Hui Zhu; Nan Tian; Yujuan La; Ke Huang; Lei Jiang; Guang He; Linhan Gao; Xinzhi Zhao; et al. (Molecular and Cellular Biochemistry, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

RNA interference against interleukin-5 attenuates airway inflammation and hyperresponsiveness in an asthma model - Shao-xing Chen; Feng-ying Huang; Guang-hong Tan; Cai-chun Wang; Yong-hao Huang; Hua Wang; Song-lin Zhou; Fan Chen; Ying-ying Lin; Jun-bao Liu (Journal of Zhejiang University-SCIENCE B, 2009)

The LLA23 protein translocates into nuclei shortly before desiccation in developing pollen grains and regulates gene expression in Arabidopsis - Chin-Ying Yang; Chih-Hsien Wu; Guang Yuh Jauh; Jong-Chin Huang; Chin-Chung Lin; Co-Shine Wang (Protoplasma, 2008)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

A fusion protein containing murine vascular endothelial growth factor and tissue factor induces thrombogenesis and suppression of tumor growth in a colon carcinoma model - Feng-ying Huang; Yue-nan Li; Hua Wang; Yong-hao Huang; Ying-ying Lin; Guang-hong Tan (Journal of Zhejiang University-SCIENCE B, 2008)

Compensatory growth responses to clipping defoliation in Leymus chinensis (Poaceae) under nutrient addition and water deficiency conditions - Wei Zhao; Shi-Ping Chen; Guang-Hui Lin (Plant Ecology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Apoptosis induced by ardipusilloside III through BAD dephosphorylation and cleavage in human glioblastoma U251MG cells - Hong Lin; Xiang Zhang; Guang Cheng; Hai-Feng Tang; Wei Zhang; Hai-Ning Zhen; Jin-Xiang Cheng; Bo-Lin Liu; Wei-Dong Cao; Wen-Peng Dong; Peng Wang (Apoptosis, 2008)

Positive association between OLIG2 and schizophrenia in the Chinese Han population - Ke Huang; Wei Tang; Ruqi Tang; Zhao Xu; Zhangdong He; Zhiqiang Li; Yifeng Xu; Xingwang Li; Guang He; Guoying Feng; Lin He; YongYong Shi (Human Genetics, 2008)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Quantitative studies on phosphorus transference occuring between Microcystis aeruginosa and its attached bacterium (Pseudomonas sp.) - Lijuan Jiang; Liuyan Yang; Lin Xiao; Xiaoli Shi; Guang Gao; Boqiang Qin (Hydrobiologia, 2007)

Facial pain induces the alteration of transient receptor potential vanilloid receptor 1 expression in rat trigeminal ganglion - Lei Pei; Chuan-You Lin; Jia-Pei Dai; Guang-Fu Yin (Neuroscience Bulletin, 2007)

The functional haplotype of peptidylarginine deiminase IV (S55G, A82V and A112G) associated with susceptibility to rheumatoid arthritis dominates apoptosis of acute T leukemia Jurkat cells - Hui-Chih Hung; Chien-Yu Lin; Ya-Fan Liao; Pei-Chen Hsu; Gregory J. Tsay; Guang-Yaw Liu (Apoptosis, 2007)

Sustainable Water Quality Management Framework and a Strategy Planning System for a River Basin - Ching-Ho Chen; Wei-Lin Liu; Horng-Guang Leu (Environmental Management, 2006)

(1S)-1-Ethyl-2-Methylpropyl 3,13-Dimethylpentadecanoate: Major Sex Pheromone Component of Paulownia Bagworm, Clania variegata - Regine Gries; Grigori Khaskin; Zhong-Xing Tan; Bo-Guang Zhao; G. G. Skip King; Aleksander Miroshnychenko; Guo-Qiang Lin; Marc Rhainds; Gerhard Gries (Journal of Chemical Ecology, 2006)

Degradability of atrazine, cyanazine, and dicamba in methanogenic enrichment culture microcosms using sediment from the Pearl River of Southern China - Chen Lin; Ji-Guang Gu; Chuanling Qiao; Shunshan Duan; Ji-Dong Gu (Biology and Fertility of Soils, 2006)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)

Site-specific phosphorylation of L-form starch phosphorylase by the protein kinase activity from sweet potato roots - Guang-Huar Young; Han-Min Chen; Chi-Tsai Lin; Kuang-Ching Tseng; Jiann-Shing Wu; Rong-Huay Juang (Planta, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

A Season-dependent Variation of Genotoxicity of Surface Water Samples from Taihu Lake, Yangzte Delta - Jian-Yong Wu; Lei Shen; Guang Gao; Guo-Fang Lin; Xin Ke; Jian-Hua Shen (Environmental Monitoring and Assessment, 2004)

Relationship between resort life cycle and residents’ perception and attitude - Xiao-zhong Yang; Lin Lu; Guang-sheng Zhang; Song Lu; Guo-fu Xuan (Chinese Geographical Science, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Overexpression, Purification, and Characterization of the Recombinant Leucine Aminopeptidase II of Bacillus stearothermophilus - Lih-Ying Kuo; Guang-Yuh Hwang; Yu-Jing Lai; Shin-Ling Yang; Long-Liu Lin (Current Microbiology, 2003)

Antioxidant enzymes and trace elements in hemodialyzed patients - Chi-Ken Chen; Jinn-Ming Liaw; Jih-Guang Juang; Te-Hsien Lin (Biological Trace Element Research, 1997)

The epidemiology and surveillance of blood lead in Taiwan (R.O.C.): A report on the PRESS-BLL project - T.-N. Wu; Chen-Yang Shen; Saou-Hsing Liou; Guang-Yang Yang; K.-N. Ko; Show-Lin Chao; Chao-Chun Hsu; P.-Y. Chang (International Archives of Occupational and Environmental Health, 1997)